Glass-based article including a stress profile including two regions and method of manufacture - Patents.com
Patent Information
- Application Number
- JP2023158257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-04-08
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2037-04-07
AI Technical Summary
【0049】 以上の概要および以下の詳細な説明の両方は、単に例示的なものであり、請求項の性質および特性を理解するための概要または枠組みを提供することが意図されることを理解されたい。添付の図面は、さらなる理解を得るために含まれ、本明細書に含まれかつ本明細書の一部を構成する。図面は、1つ以上の実施形態を示し、本明細書の記述とともに種々の実施形態の原理および操作を説明する役割を果たす。
Smart Images

Figure 0007645327000035 
Figure 0007645327000036 
Figure 0007645327000037
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] Under Section 119 of the United States Patent Act, a divisional application (Patent Application No. 2021-101484) filed on June 18, 2021 was granted based on Patent Application No. 2018-540470 (International Registration Date: April 7, 2017), which is an international application claiming the benefit of priority to U.S. Provisional Patent Application No. 62 / 320109, filed on April 8, 2016, and which entered the national phase in Japan. This application is a divisional application whose parent is Patent Application No. 2021-101484. [Technical field]
[0002] The present disclosure relates to glass-based articles that exhibit improved damage resistance, including improved fracture resistance, and in particular to fusion-formable glass and glass-ceramic articles that exhibit a non-zero metal oxide concentration gradient or concentration that varies along a substantial portion of their thickness. The present disclosure also relates to glass-based articles that include a stress profile that includes two regions with different tangents. [Background technology]
[0003] Glass-based articles are often subjected to violent impacts that can generate large flaws in the surface of such articles. Such flaws can extend from the surface to a depth of up to about 200 micrometers. Traditionally, thermally strengthened glass is used to prevent breakage caused by the introduction of such flaws into the glass, because thermally strengthened glass often exhibits a large compressive stress (CS) layer (e.g., about 21% of the total glass thickness), which can prevent further propagation of the flaw into the glass and therefore breakage. An example of a stress profile obtained by thermal strengthening is shown in FIG. 1. In FIG. 1, a heat-treated glass article 100 includes a first surface 101, a thickness t1, and a surface CS 110. The heat-treated glass article 100 exhibits a CS that decreases from the first surface 101 to a depth of compression 130 (DOC), which is the depth at which the stress changes from compressive stress to tensile stress as defined herein, and reaches a maximum central tension (CT) 120.
[0004] Thermal strengthening is currently limited to thick glass-based articles (i.e., glass-based articles having a thickness t1 of about 3 millimeters or more) because it is necessary to create a sufficient temperature gradient between the center and the surface of such articles to achieve thermal strengthening and the desired residual stress. In many applications, such as displays (e.g., consumer electronics, such as mobile phones, tablets, computers, navigation systems, etc.), architecture (e.g., windows, shower panels, countertops, etc.), transportation (e.g., automobiles, trains, aircraft, ocean-going ships, etc.), appliances, or any application that requires a thin, lightweight article while still requiring good fracture resistance, such articles are undesirable or impractical.
[0005] Although chemical strengthening is not limited by the thickness of the glass-based article in the same way as thermal strengthening, known chemically strengthened glass-based articles do not exhibit the stress profile of thermally strengthened glass-based articles. An example of a stress profile obtained by chemical strengthening (e.g., by an ion exchange process) is shown in FIG. 2. In FIG. 2, a chemically strengthened glass-based article 200 includes a first surface 201, a thickness t2, and a surface CS 210. The glass-based article 200 exhibits a CS that decreases from the first surface 201 to a DOC 230 at a depth where the stress changes from compressive stress to tensile stress as defined herein, reaching a maximum CT 220. As shown in FIG. 2, such a profile exhibits a substantially flat CT region, i.e., a CT region with a constant or nearly constant tensile tension along at least a portion of the CT region. Known chemically strengthened glass-based articles often exhibit a smaller maximum CT value compared to the maximum median value shown in FIG. 1. Summary of the Invention [Problem to be solved by the invention]
[0006] It would be desirable to provide a glass-based article and a method of providing such a glass article having a relatively high compressive stress at a surface of the article and a first stress profile region having a steep slope or tangent and a second stress profile region having a less steep profile region. [Means for solving the problem]
[0007] A first aspect of the present disclosure relates to a glass-based article comprising a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t), a concentration of metal oxide that is non-zero and varies along a thickness range of about 0·t to about 0.3·t, and a central tensile (CT) region comprising a maximum CT of less than about 80 MPa. In one or more embodiments, when the glass-based article breaks, the glass-based article breaks within a square inch (6.4516 cm). 2 In one or more embodiments, when the glass-based article is broken, the glass-based article breaks into at least two pieces per square inch. 2 At least one shard per square inch 2 ) into up to 40 pieces.
[0008] In one or more embodiments, the concentration of the metal oxide is non-zero and varies along the entire thickness. In one or more embodiments, the metal oxide generates stress along the thickness range. The monovalent ions of the metal oxide can have the largest ionic diameter of all of the monovalent ions of the metal oxide in the glass-based substrate. The concentration of the metal oxide can decrease from the first surface to a value at a point between the first surface and the second surface, and increase from that value to the second surface. For example, the concentration of the metal oxide at the first surface can be about 1.5 times the concentration of the metal oxide at a depth equal to about 0.5·t. In some cases, the concentration of the metal oxide is about 0.05 mol % or more (e.g., in the range of about 1 mol % to about 15 mol %) throughout the thickness. The metal oxide can include any one or more of Li2O, Na2O, KO, Rb2O, and Cs2O. In one or more embodiments, a concentration gradient of the metal oxide can exist within the CT region of the glass-based article.
[0009] In one or more embodiments, the glass-based article comprises a stress profile extending along the thickness, where all points of the stress profile between about 0·t up to 0.3·t and greater than 0.7·t in the thickness range comprise a tangent having a slope less than about −0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer. In some embodiments, the stress profile comprises a maximum CS, a DOC, and a maximum CT less than about 80 MPa, where the ratio of the maximum CT to the maximum absolute value of CS is in the range of about 0.01 to about 0.2, and the DOC is about 0.1·t or greater. When the glass-based article of one or more embodiments breaks, the glass-based article may be subjected to a stress profile of less than 1 square inch (about 6.4516 cm 2 ) will be broken into at least two pieces.
[0010] The glass-based article of one or more embodiments can include a surface compressive stress (CS) of about 300 MPa or more, or about 500 MPa or more. In some embodiments, the glass-based article includes a surface CS of about 200 MPa or more, and a chemical depth of layer of about 0.4·t or more. In one or more embodiments, the CS can extend from the first surface to the DOC, where the DOC is about 0.1·t or more. The glass-based article of some embodiments exhibits a ratio of maximum CT to absolute value of surface CS (which can include maximum CS) in the range of about 0.01 to about 0.2. Optionally, the absolute value of surface CS is greater than maximum CT.
[0011] In one or more embodiments, the glass-based article comprises a first metal oxide concentration and a second metal oxide concentration, the first metal oxide concentration is in a range of about 0 mol % to about 15 mol % from a first thickness range of about 0·t to about 0.5·t and the second metal oxide concentration is in a range of about 0 mol % to about 10 mol % from a second thickness range of about 0 micrometers to about 25 micrometers. Optionally, the glass-based article comprises a third metal oxide.
[0012] In one or more embodiments, the glass-based article comprises a concentration of metal oxide that is non-zero and varies along a thickness range of about 0·t to about 0.3·t (or about 0·t to about 0.4·t, or about 0·t to about 0.45·t), a surface compressive stress of about 200 MPa or greater, and a CT region having a maximum CT (MPa) of less than about 80 MPa.
[0013] The glass-based article can have a thickness t of about 3 millimeters or less, or about 1 millimeter or less. The glass-based article can have an amorphous structure, a crystalline structure, or a combination of both. The glass-based article can exhibit a transmittance of about 88% or greater over a wavelength range from about 380 nm to about 780 nm. Additionally, in some embodiments, the glass-based article can exhibit an L of about 88 or greater under CIE illuminant F02. * Value, a in the range of about -3 to about +3 * value, and b in the range of about -6 to about +6 * The CIELAB color space coordinates of the value can be indicated.
[0014] In one or more embodiments, the glass-based article comprises a Young's modulus of less than 80 GPa. The glass-based article comprises a liquidus viscosity of about 100 kilopoise (kP) (10 kPa·s) or greater.
[0015] The glass-based article can include compositions having any one or more of: compositions comprising greater than about 15 mol% combined Al2O3 and Na2O; compositions comprising greater than about 4 mol% Na2O; compositions that are substantially free of B2O3, ZnO, or both B2O3 and ZnO; and compositions that include a non-zero amount of P2O5.
[0016] The glass-based article has a thickness of about 450 μm at about 460° C. 2 / h and DOC greater than about 0.15·t, with absolute values of surface CS greater than 1.5 times the maximum CT.
[0017] In some embodiments, the glass-based article has a viscosity of about 0.7 MPa m 1 / 2 Fracture toughness (K 1C ).
[0018] In one or more embodiments, the glass-based article has a thermal conductivity of greater than about 0 J / m2 to about 20 J / m2. 2 The stored tensile energy is less than 100 MPa.
[0019] In one or more embodiments, the glass-based article comprises a stress profile including a CS region and a CT region, the CT region being Stress(x)=MaxCT-(((MaxCT·(n+1)) / 0.5 n )·|(x / t)-0.5| n), where MaxCT is the maximum CT value and is a positive value in units of MPa, x is the position along the thickness (t) in units of micrometers, and n is between 1.5 and 5. In some embodiments, the CT region includes a maximum CT value in the range of about 50 MPa to about 250 MPa, and the maximum CT value is at a depth in the range of about 0.4t to about 0.6t. In some cases, from a depth in the range of about 0t to about 0.1t micrometers, the stress profile includes a slope in the range of about 20 MPa / micrometer to about 200 MPa / micrometer. In one or more embodiments, the stress profile is defined by a combination of multiple error functions when measured from 0.5t to the surface.
[0020] A second aspect of the present disclosure relates to the use of a glass composition in a reinforced glass-based article comprising (in mole percent) SiO2 in an amount ranging from about 60 to about 75, Al2O3 in an amount ranging from about 12 to about 20, B2O3 in an amount ranging from about 0 to about 5, Li2O in an amount ranging from about 2 to about 8, Na2O in an amount greater than 4, P2O5 in a non-zero amount, MgO in an amount ranging from about 0 to about 5, ZnO in an amount ranging from about 0 to about 3, and CaO in an amount ranging from about 0 to about 5, wherein the glass composition is ion-exchangeable and amorphous, the total amount of Al2O3 and Na2O is greater than about 15 mole percent, the glass composition is substantially free of nucleating agents, and the glass composition comprises a liquidus viscosity of about 100 kP (10 kPa s) or greater. In one or more embodiments, the glass composition is substantially free of B2O3, ZnO, or both B2O3 and ZnO.
[0021] A third aspect of the present disclosure relates to a glass substrate comprising a composition comprising, in mole percent, SiO in an amount ranging from about 60 to about 75, AlO in an amount ranging from about 12 to about 20, BO in an amount ranging from about 0 to about 5, LiO in an amount ranging from about 2 to about 8, NaO in an amount greater than about 4, MgO in an amount ranging from about 0 to about 5, ZnO in an amount ranging from about 0 to about 3, CaO in an amount ranging from about 0 to about 5, and a non-zero amount of P0, wherein the glass substrate is ion-exchangeable and amorphous, the total amount of AlO and NaO in the composition is greater than about 15 mole percent, the glass composition is substantially free of nucleating agents, and comprises a liquidus viscosity of about 100 kP (10 kPa s) or greater.
[0022] In some embodiments, the glass substrate is amorphous and strengthened, the Na2O concentration is varied, the composition is substantially free of nucleating agents, the total amount of Al2O3 and Na2O in the composition is greater than about 15 mol %, and the composition comprises a liquidus viscosity of about 100 kP (10 kPa s) or greater. In some embodiments, the glass substrate comprises a non-zero amount of P2O5.
[0023] A fourth aspect of the present disclosure relates to a glass-based article comprising a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm, and a stress profile extending along the thickness (t), wherein at least one point of the stress profile within a first thickness range of about 0·t up to 0.020·t and greater than 0.98·t includes a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer, and all points of the stress profile within a second thickness range of about 0.035·t to less than 0.965·t include a tangent having a slope of about −15 MPa / micrometer to about 15 MPa / micrometer, wherein the stress profile includes a surface CS of about 200 MPa to about 1100 MPa, and wherein the stress profile includes a DOC in the range of about 0.1·t to 0.25·t. In some embodiments, all points of the stress profile within a first thickness range from about 0·t up to 0.020·t and greater than 0.98·t include a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer.
[0024] In one or more embodiments, all points of the stress profile within the second thickness range include a tangent having a slope between about -2 MPa / micrometer and about 2 MPa / micrometer.
[0025] In one or more embodiments, all points of the stress profile within the second thickness range from about 0.025·t to less than 0.975·t include a tangent having a slope from about -15 MPa / micrometer to about 15 MPa / micrometer, hi some embodiments, all points of the stress profile within the second thickness range include a tangent having a slope from about -2 MPa / micrometer to about 2 MPa / micrometer.
[0026] In one or more embodiments, all points of the stress profile within the second thickness range from about 0.02·t to less than 0.98·t include a tangent having a slope from about −15 MPa / micrometer to about 15 MPa / micrometer, hi some embodiments, all points of the stress profile within the second thickness range include a tangent having a slope from about −2 MPa / micrometer to about 2 MPa / micrometer.
[0027] In one or more embodiments, the stress profile within the second thickness range forms a power law profile having a power exponent between about 1.2 and 3.2, hi some embodiments, the power exponent is between about 1.3 and 2.8.
[0028] In one or more embodiments, the surface CS is from about 300, 350, 400, 450, 500, 550, 600, 610, 620 MPa to about 650, 700, 750, 800, 850, 900, 950, 1000 or 1100 MPa.
[0029] In one or more embodiments, at least one point of the stress profile within the first thickness range includes a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In one or more embodiments, all points of the stress profile within the first thickness range include a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In some embodiments, all points of the stress profile within the first thickness range include a tangent having a slope of about -140 MPa / micrometer to about -35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer. In some embodiments, at least one point of the stress profile within the first thickness range includes a tangent having a slope of about -140 MPa / micrometer to about -35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer.
[0030] In one or more embodiments, at least one point of the stress profile within a first thickness range of about 0·t up to 0.025·t and greater than 0.975·t includes a tangent having a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer. In one or more embodiments, all points of the stress profile within a first thickness range of about 0·t up to 0.025·t and greater than 0.975·t include a tangent having a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer. In some embodiments, at least one point of the stress profile within a first thickness range includes a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In some embodiments, at least one point, and in other embodiments, all points, of the stress profile within the first thickness range include a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In some embodiments, at least one point, and in other embodiments, all points, of the stress profile within the first thickness range include a tangent having a slope of about -140 MPa / micrometer to about -35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer.
[0031] In one or more embodiments at least one point, and in other embodiments all points, of the stress profile within the first thickness range from about 0·t up to 0.035·t and above 0.965·t include a tangent with a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer. In some embodiments at least one point, and in other embodiments all points, of the stress profile within the first thickness range include a tangent with a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In some embodiments at least one point, and in other embodiments all points, of the stress profile within the first thickness range include a tangent with a slope of about -140 MPa / micrometer to about -35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer.
[0032] In one or more embodiments, the first thickness range is achieved by ion exchange in a K-containing salt.
[0033] In one or more embodiments, the second thickness range is achieved by ion exchange in a Na-containing salt.
[0034] In one or more embodiments, the stress profile is obtained using one ion exchange step.
[0035] In one or more embodiments, the stress profile is obtained using two or more ion exchange steps.
[0036] In one or more embodiments, the surface CS is between about 690 MPa and 950 MPa.
[0037] In one or more embodiments, the glass-based article comprises a composition between about 0.5 mol % P2O5 and 10 mol % P2O5.
[0038] A fifth aspect of the present disclosure relates to a glass-based article comprising a central surface, the central surface comprising about 2 to about 20 mol % LiO, a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm, and a stress profile extending along the thickness (t), wherein at least one point of the stress profile within the first thickness range of about 0·t up to 0.020·t and greater than 0.98·t comprises a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer, the stress profile comprising a surface CS of about 200 MPa to about 1100 MPa, and the stress profile comprising a DOC in the range of about 0.05·t to 0.25·t. In some embodiments, all points of the stress profile within a first thickness range from about 0·t up to 0.020·t and greater than 0.98·t include a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer.
[0039] In one or more embodiments, the first thickness range is achieved by ion exchange in a K-containing salt.
[0040] In one or more embodiments, the second thickness range is achieved by ion exchange in a Na- or K-containing salt.
[0041] In one or more embodiments, the stress profile is obtained using one ion exchange step.
[0042] In one or more embodiments, the stress profile is obtained using two or more ion exchange steps.
[0043] In one or more embodiments, the surface CS is in the range of about 690 MPa to 950 MPa.
[0044] In one or more embodiments, the stress profile within the second thickness range forms a power law profile having a power exponent between about 1.2 and 3.4, hi some embodiments, the power exponent is between about 1.3 and 2.8.
[0045] In one or more embodiments, the glass-based article comprises a composition comprising about 0.5 mol % P2O5 to 10 mol % P2O5.
[0046] In one or more embodiments, the central surface further comprises a composition comprising about 0.5 mol % to 20 mol % Na2O. In some embodiments, the central surface further comprises a composition comprising about 2 mol % to 10 mol % Li2O. In some embodiments, the concentration of Na2O within the central surface of the glass article is about 5 mol % to 16 mol %. In some embodiments, the concentration of Na2O within the central surface of the glass article is about 10 mol % to 15 mol %. In some embodiments, the concentration of Li2O within the central surface of the glass article is about 3 mol % to 10 mol %.
[0047] In one or more embodiments, a method is provided for obtaining the stress profile described herein. Such a method requires a relatively long ion exchange time, either by one ion exchange or by two or more ion exchanges. According to one or more embodiments, the ion exchange time is more than 1 hour, more than 1.5 hours, more than 2 hours, more than 2.5 hours, more than 3 hours, more than 3.5 hours, more than 4 hours, more than 4.5 hours, more than 5 hours, more than 5.5 hours, more than 6 hours, more than 6.5 hours, more than 7 hours, more than 7.5 hours, and more than 8 hours.
[0048] Additional features and advantages are set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from the following description, or will be learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.
[0049] It should be understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding, and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments, and together with the description herein, serve to explain the principles and operation of the various embodiments. [Brief description of the drawings]
[0050] [Figure 1] FIG. 1 is a cross-sectional view through the thickness of a known thermally strengthened glass article. [Diagram 2] FIG. 1 is a cross-sectional view through the thickness of a known chemically strengthened glass article. [Diagram 3] FIG. 2 is a cross-sectional view through the thickness of a chemically strengthened glass-based article according to one or more embodiments of the present disclosure. [Figure 4] FIG. 2 is a schematic cross-sectional view of a ring-on-ring device. [Diagram 5] 1 is a graph showing maximum CT values of Examples 1A-1G as a function of ion-exchange time. [Figure 6] 1 is a graph showing the measured stress of Example 1E as a function of the depth extending from the surface of the glass-based article into the glass-based article of Example 1E. [Figure 7] 1 is a graph showing the failure load values of the glass-based article according to Example 2A after polishing at various loads or pressures. [Figure 8] 1 is a graph showing the height at which a glass-based article according to Example 2A broke after being dropped onto 180 grit abrasive paper and then 30 grit abrasive paper. [Figure 9] 1 is a graph showing the height at which glass-based articles according to Example 3A and Comparative Example 3B broke after being dropped onto 30 grit abrasive paper. [Figure 10] 1 is a graph comparing the average failure load of glass-based articles according to Example 3A and Comparative Example 3B after abrasion at a load or pressure of 25 psi (172 kPa). [Figure 11]1 is a graph comparing the average failure load of glass-based articles according to Example 3A and Comparative Example 3B after abrasion at a load or pressure of 45 psi (310 kPa). [Figure 12] 1 is a graph showing the stress profile of Examples 4A-1 to 4A-6 as a function of depth. [Figure 13] 1 is a graph showing maximum CT and DOC values of Examples 4A-1 to 4A-6 as a function of ion exchange time. [Figure 14] 1 is a graph showing the stress profiles of Examples 4B-1 to 4B-6 as a function of depth. [Figure 15] 1 is a graph showing maximum CT and DOC values of Examples 4B-1 to 4B-6 as a function of ion exchange time. [Figure 16] 1 is a graph showing the stress profile of Examples 4C-1 to 4C-6 as a function of depth. [Figure 17] 1 is a graph showing maximum CT and DOC values of Examples 4C-1 to 4C-6 as a function of ion exchange time. [Figure 18] 1 is a graph showing the stress profiles of Examples 4D-1 to 4D-6 as a function of depth. [Figure 19] 1 is a graph showing maximum CT and DOC values of Examples 4D-1 to 4D-6 as a function of ion exchange time. [Figure 20] 1 is a graph showing the stress profile of Comparative Example 5A and Example 5B as a function of depth. [Figure 21] 1 is a graph showing the stored tensile energy of Comparative Example 5A and Example 5B as a function of maximum CT. [Figure 22] 1 is a graph showing the stored tensile energy of Comparative Example 5C and Example 5D as a function of maximum CT. [Diagram 23] 1A-1D are cross-sectional views through the thickness of four chemically strengthened glass-based articles according to one or more embodiments of the present disclosure. [Figure 24]1 is a graph showing normalized microprobe concentration profiles of K, Na, and Li for a chemically strengthened glass-based article according to one or more embodiments of the present disclosure. [Diagram 25] 1A-1D are images of scratch test results for four chemically strengthened glass-based articles according to one or more embodiments of the present disclosure. [Figure 26] 1 is a graph comparing the average failure load of glass-based articles according to one or more embodiments of the present disclosure. [Figure 27A] FIG. 1 is a schematic cross-sectional view of the primary mechanisms of damage introduction and fracture by bending that typically occur in glass-based articles used in mobile or handheld electronic devices. [Figure 27B] FIG. 1 is a schematic cross-sectional view of one embodiment of an apparatus used to perform the Inverted Ball on Sandpaper (IBoS) test described in the present disclosure. [Figure 28] 1 is a flow chart of a method for performing an IBoS test on an apparatus described herein. [Figure 29] FIG. 1 is a side view of a testing apparatus for glass-based articles. [Diagram 30] FIG. 30 is a side view of a portion of the testing apparatus shown in FIG. 29. [Diagram 31] FIG. 30 is a rear perspective view of the testing apparatus shown in FIG. 29. [Diagram 32] FIG. 30 is a front perspective view of the testing apparatus shown in FIG. 29. [Diagram 33] FIG. 1 is a side view of a testing apparatus for glass-based articles. [Diagram 34] FIG. 30 is a side view of a portion of the testing apparatus shown in FIG. 29. [Diagram 35] FIG. 30 is a schematic diagram of an alternative configuration of a portion of the testing apparatus shown in FIG. 29. [Diagram 36] 1 is a graph illustrating various stress profiles according to some embodiments. [Figure 37] 1 is a graph showing IBoS test results for samples according to some embodiments. [Figure 38] 1 is a graph showing surface impact threshold test results for samples according to some embodiments and several comparative samples. [Figure 39]1 is a graph showing edge impact test results for samples according to some embodiments. [Figure 40A] FIG. 1 is a plan view of an exemplary electronic device incorporating any of the glass-based articles disclosed herein. [Figure 40B] FIG. 40B is a perspective view of the representative electronic device of FIG. 40A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] Reference will now be made in detail to various embodiments, examples of which are illustrated in the accompanying examples and drawings.
[0052] In the following description, like reference characters indicate like or corresponding parts throughout the several figures shown in the drawings. It is also understood that terms such as "top", "bottom", "outer", "inner" and the like are words of convenience and should not be construed as terms of limitation, unless otherwise specified. Furthermore, whenever a group is described as comprising at least one of a group of elements and combinations thereof, it is understood that the group can comprise, consist essentially of, or consist of any number of the described elements, either individually or in combination with each other. Similarly, whenever a group is described as consisting of at least one of a group of elements or combinations thereof, it is understood that the group can consist of any number of the described elements, either individually or in combination with each other. Unless otherwise specified, when a range of values is described, this includes both the upper and lower limits of the range and any ranges therebetween. As used herein, the indefinite articles "a", "an" and the corresponding definite article "the" mean "at least one" or "one or more" unless otherwise specified. It is also understood that the various features disclosed in this specification and in the drawings can be used in any and all combinations.
[0053] As used herein, the terms "glass-based article" and "glass-based substrate" are used in the broadest sense to include any object made entirely or partially of glass. Glass-based articles include laminates of glass and non-glass materials, laminates of glass and crystalline materials, and glass ceramics (including amorphous and crystalline phases). Unless otherwise specified, all compositions are expressed in mole percent (mol%).
[0054] It should be noted that the terms "substantially" and "about" can be used herein to express the degree of inherent uncertainty that may result from any quantitative comparison, value, measurement, or other representation. These terms are also used herein to express the extent to which a quantitative representation can vary from the stated standard without causing a change in the basic functionality of the subject matter under consideration. Thus, for example, a glass-based article that is "substantially free of MgO" is a glass-based article in which MgO is not actively added or batch processed into the glass-based article, but may be present in very small amounts as a contaminant.
[0055] As used herein, the term "about" means that amounts, sizes, formulations, parameters and other quantities and characteristics are not and need not be exact, but may be approximate and / or larger or smaller as necessary, reflecting tolerances, conversion factors, rounding, measurement errors, and the like, and other factors well known to those skilled in the art. When the term "about" is used to describe a value or an end point of a range, the present disclosure should be understood to include the specific value or end point referred to. When "about" is described or not described as a numerical value or an end point of a range herein, the numerical value or end point of a range is intended to include two embodiments, that is, an embodiment modified by "about" and an embodiment not modified by "about". It should be further understood that each end point of a range is valid both in relation to the other end point and independently of the other end point.
[0056] Unless otherwise specified, all temperatures are expressed in degrees Celsius (° C.). As used herein, the term "softening point" refers to the point at which the viscosity of a glass drops to about 10 7.6 Poise (P) (10 6 The term "annealing point" refers to the temperature at which the viscosity of the glass reaches approximately 10 Pa s. 13.2 Poise (10 12.2 The temperature at which the force of 200 poise is reached is called the 200 poise temperature (T 200P The term "temperature at which the viscosity of the glass is approximately 200 poise (20 Pa s)" is used to refer to the temperature at which the viscosity of the glass is approximately 200 poise (20 Pa s). 11 The term "Poise temperature" refers to the temperature at which the viscosity of a glass drops to approximately 10 11 Poise (10 10 The temperature at which the force of 35 kP is reached is called the 35 kP temperature (T 35kP The term "160 kP temperature (T )" refers to the temperature at which the viscosity of the glass is approximately 35 kilopoise (kP) (3.5 kPa s). 160kP ) refers to the temperature at which the viscosity of the glass is approximately 160 kP (16 kPa s).
[0057] Referring generally to the drawings, and particularly to Figures 1-3, it will be understood that these figures are intended to illustrate particular embodiments and are not intended to limit the present disclosure or the claims appended hereto. The drawings are not necessarily to scale, and certain features and views of the drawings may be shown exaggerated in scale or illustrated diagrammatically for clarity and conciseness.
[0058] As used herein, DOC refers to the depth within a glass-based article where stress changes from compressive to tensile. At the DOC, the stress traverses (e.g., 130 in FIG. 1 ) from positive (compressive) to negative (tensile), thus exhibiting a stress value of zero.
[0059] As used herein, the terms "chemical depth", "chemical depth of layer", and "chemical layer depth" can be used interchangeably and refer to the depth to which metal oxide or alkali metal oxide ions (e.g., metal ions or alkali metal ions) diffuse into a glass-based article and the depth at which the ion concentration reaches a minimum as measured by electron probe microanalysis (EPMA) or glow discharge optical emission spectroscopy (GD-OES). In particular, an assessment of Na2O diffusion depth or Na+ ion concentration can be determined using EPMA and a surface stress meter (described in more detail below).
[0060] According to the convention commonly used in the art, compressive stresses are expressed as negative (<0) and tensile stresses are expressed as positive (>0) stresses unless otherwise specified, however, throughout the description herein, CS is expressed as a positive or absolute value, i.e., CS=|CS| as described herein.
[0061] Described herein are thin, chemically strengthened glass-based articles, including glasses such as alkali-containing glasses and silicate glasses, including glass ceramics, that can be used as cover glasses for mobile electronic devices and touchable displays. The glass-based articles can also be used in displays (or as display devices) (e.g., billboards, point of sale systems, computers, navigation systems, etc.), building articles (walls, fixtures, panels, windows, etc.), transportation articles (e.g., automotive applications, trains, aircraft, ocean-going ships, etc.), appliances (e.g., washers, dryers, dishwashers, refrigerators, etc.), or any article that requires some degree of fracture resistance.
[0062] In particular, the glass-based articles described herein exhibit stress profiles that are only achievable by thermal strengthening of thin, typically thick, glass articles (e.g., having a thickness of about 2 mm or 3 mm or more). The glass-based articles exhibit unique stress profiles along their thickness. In some cases, the glass-based articles described herein exhibit greater surface CS than thermally strengthened glass articles. In one or more embodiments, the glass-based articles have a compressive stress layer that extends deeper within the glass-based article (in which CS decreases and increases more gradually than known chemically strengthened glass-based articles), thereby allowing such glass-based articles to exhibit substantially improved fracture resistance, even when the glass-based article or a device containing it is dropped onto a hard surface (e.g., granite) or a hard, rough surface (e.g., asphalt). The glass-based articles of one or more embodiments exhibit greater maximum CT values than some known chemically strengthened glass substrates.
[0063] CS and potassium ion penetration depth ("potassium DOL"), or chemical layer depth "DOL" or "chemical DOL", which typically refers to the depth of compressive stress, especially of surface spikes, typically caused by potassium ions, are measured using means well known in the art. As used herein, DOC refers to the depth at which stress changes from compressive to tensile in the chemically strengthened alkali aluminosilicate glass article described herein. DOC can be measured by FSM or scattered light polariscope (SCALP), depending on the ion exchange treatment. When stress in the glass article is caused by exchange of potassium ions into the glass article, FSM is used to measure DOC. When stress is caused by exchange of sodium ions into the glass article, SCALP is used to measure DOC. In cases where stress in a glass article is caused by exchange of both potassium and sodium ions, the DOC is measured by SCALP because it is believed that the sodium exchange depth indicates the DOC and the potassium ion exchange depth indicates a change in the magnitude of compressive stress (but not a change in stress from compressive to tensile), and the potassium ion exchange depth in such glass articles is measured by FSM.
[0064] The potassium DOL is distinct from the DOC because it indicates the potassium penetration depth as a result of the ion exchange process. For the articles described herein, the potassium DOL is typically smaller than the DOC. The CS and potassium DOL are measured by a surface stress meter (FSM) using commercially available equipment such as the FSM-6000 manufactured by Orihara Seisakusho Co., Ltd. (Japan). Surface stress measurements rely on accurately measuring the stress optical coefficient (SOC), which is related to the birefringence of the glass. The SOC is measured by a modified version of Procedure C described in ASTM standard C770-98 (2013), entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the entire contents of which are incorporated herein by reference. The modified version includes the use of a glass disk as a test specimen having a thickness of 5-10 mm and a diameter of 12.7 mm, which is isotropic, uniform, has a hole drilled in the center, and both sides are polished and parallel. The modified version also includes the calculation of the maximum applied force Fmax. This force should be sufficient to obtain a compressive stress of at least 20 MPa. Fmax is calculated as follows: Fmax=7.854 D h During the ceremony, Fmax = force in newtons D = diameter of the disk h = optical path thickness For each applied force, the stress is calculated as follows: σ MPa =8F / (π D h) During the ceremony, F = force in newtons D = diameter of the disk h = optical path thickness It is.
[0065] The maximum CT value is measured using a scattered light polariscope (SCALP). The refractive near-field (RNF) method or SCALP can be used to measure the stress profile. When the RNF method is used, the maximum CT value obtained by SCALP is utilized. In particular, the stress profile measured by the RNF method is force balanced and calibrated against the maximum CT value obtained by the SCALP measurement. The RNF method is described in U.S. Pat. No. 8,854,623, entitled "Systems and methods for measuring a profile characteristic of a glass sample," which is incorporated herein by reference in its entirety. In particular, the RNF method includes the steps of placing a glass-based article adjacent to a reference block, generating a polarization-switched light beam that is switched between orthogonal polarizations at a rate of 1 Hz to 50 Hz, measuring the amount of power output of the polarization-switched light beam, and generating a polarization-switched reference signal, the measured amounts of power output of each of the orthogonal polarizations being within 50% of each other. The method further includes transmitting the polarization switched light beam through the glass sample and the reference block at various depths in the glass sample, and then relaying the transmitted polarization switched light beam to a signal photodetector using relay optics, which generates a polarization switched detector signal. The method also includes dividing the detector signal by the reference signal to form a normalized detector signal, and determining profile characteristics of the glass sample from the normalized detector signal. The RNF profile is then smoothed and used for the CT domain. As previously mentioned, the FSM technique is used for the slope of the stress profile in the surface CS and near-surface CS domains.
[0066] As previously mentioned, the glass-based articles described herein are chemically strengthened by ion exchange and exhibit stress profiles distinct from those exhibited by known strengthened glass articles. In this disclosure, glass-based substrates are generally not strengthened, and glass-based articles generally refer to glass-based substrates that have been strengthened (e.g., by ion exchange). In this process, ions at or near the surface of the glass-based article are replaced or exchanged with larger ions having the same valence or oxidation state. In embodiments where the glass-based article comprises an alkali aluminosilicate glass, the ions in the surface layer of the glass and the larger ions are Li + (When present in glass-based articles), Na + , K + , Rb + , and Cs + Alternatively, the monovalent cations in the surface layer are Ag + The cations may be substituted with monovalent cations other than alkali metal cations such as
[0067] The ion-exchange process is typically carried out by immersing the glass-based substrate in a molten salt bath (or two or more molten salt baths) containing larger ions to be exchanged for smaller ions in the glass-based substrate. It should be noted that aqueous salt baths can also be used. Furthermore, the composition of the bath can include two or more types of larger ions (e.g., Na+ and K+) or one type of larger ion. Those skilled in the art will understand that the parameters of the ion-exchange process, such as, but not limited to, the composition and temperature of the bath, the immersion time, the number of times the glass-based article is immersed in a salt bath (or baths), the use of multiple salt baths, further steps such as annealing, washing, etc., are generally determined by the composition of the glass-based article (including the structure of the article and any crystalline phases present), and the desired DOL or DOC and CS of the glass-based article obtained by strengthening. By way of example, ion-exchange of the glass-based substrate can be carried out by immersing the glass-based substrate in at least one molten bath containing salts such as, but not limited to, nitrates, sulfates, and chlorides of larger alkali metal ions. Typical nitrates include KNO3, NaNO3, LiNO3, NaSO4, and combinations thereof. The temperature of the molten salt bath typically ranges from about 380°C up to about 450°C, while the immersion time ranges from about 15 minutes up to about 100 hours, depending on the thickness of the glass, the bath temperature, and the diffusivity of the glass. However, temperatures and immersion times different from those stated above can also be used.
[0068] In one or more embodiments, the glass-based substrate can be immersed in a molten salt bath of 100% NaNO3 having a temperature of about 370°C to about 480°C. In some embodiments, the glass-based substrate can be immersed in a molten mixed salt bath containing about 5% to about 90% KNO3 and about 10% to about 95% NaNO3. In some embodiments, the glass-based substrate can be immersed in a molten mixed salt bath containing Na2SO4 and NaNO3 and can have a wider temperature range (e.g., up to about 500°C). In one or more embodiments, the glass-based article can be immersed in a second bath after immersion in the first bath. Immersion in the second bath can include immersion in a molten salt bath containing 100% KNO3 for 15 minutes to 8 hours.
[0069] In one or more embodiments, the glass-based substrate can be immersed in a mixed molten salt bath including NaNO3 and KNO3 (e.g., 49% / 51%, 50% / 50%, 51% / 49%) having a temperature less than about 420° C. (e.g., about 400° C. or about 380° C.) for less than about 5 hours, or even about 4 hours or less.
[0070] Ion exchange conditions can be tailored to obtain a "spike" or increase in slope of the resulting stress profile at or near the surface of the glass-based article. This spike can be achieved by one bath or multiple baths, where the baths have one composition or a mixture of compositions, due to the unique nature of the glass compositions used in the glass-based articles described herein.
[0071] As shown in FIG. 3 , the glass-based article 300 of one or more embodiments includes a first surface 302 and a second surface 304 opposite the first surface, the first surface 302 and the second surface 304 defining a thickness t. In one or more embodiments, the thickness t can be about 3 millimeters or less (e.g., in the range of about 0.01 millimeters to about 3 millimeters, about 0.1 millimeters to about 3 millimeters, about 0.2 millimeters to about 3 millimeters, about 0.3 millimeters to about 3 millimeters, about 0.4 millimeters to about 3 millimeters, about 0.01 millimeters to about 2.5 millimeters, about 0.01 millimeters to about 2 millimeters, about 0.01 millimeters to about 1.5 millimeters, about 0.01 millimeters to about 1 millimeter, about 0.01 millimeters to about 0.9 millimeters, about 0.01 millimeters to about 0.8 millimeters, about 0.01 millimeters to about 0.7 millimeters, about 0.01 millimeters to about 0.6 millimeters, about 0.01 millimeters to about 0.5 millimeters, about 0.1 millimeters to about 0.5 millimeters, or about 0.3 millimeters to about 0.5 millimeters).
[0072] The glass-based article includes a stress profile that extends from a first surface 302 to a second surface 304 (or along the entire length of the thickness t). In the embodiment shown in Figure 3, the stress profile 312 as measured by the techniques described herein is shown along with a stress profile 340 estimated by FSM techniques as described herein. The x-axis represents the stress value and the y-axis represents the thickness or depth into the glass-based article.
[0073] As shown in FIG. 3, the stress profile 312 includes a CS layer 315 (having a surface CS 310), a CT layer 325 (having a maximum CT 320), and a DOC 317 where the stress profile 312 changes from compression to tension at 330. The CT layer 325 also has an associated depth or length 327 (CT region or layer). The estimated stress profile 340 includes a DOL that is greater than the DOC. As used herein, references to DOC and DOL are with respect to depth from one surface (either the first surface 302 or the second surface 304), with the recognition that such a DOC or DOL may also exist from the other surface.
[0074] Surface CS 310 can be about 150 MPa or more or about 200 MPa or more (e.g., about 250 MPa or more, about 300 MPa or more, about 400 MPa or more, about 450 MPa or more, about 500 MPa or more, or about 550 MPa or more). Surface CS 310 can be up to about 900 MPa, up to about 1000 MPa, up to about 1100 MPa, or up to about 1200 MPa. Surface CS values provided herein can also include maximum CS. In some embodiments, surface CS is less than maximum CS.
[0075] The maximum CT320 can be about 80 MPa or less, about 75 MPa or less, or about 70 MPa or less (e.g., about 60 MPa or less, about 55 MPa or less, 50 MPa or less, or about 40 MPa or less). In some embodiments, the maximum CT320 can be in the range of about 25 MPa to about 80 MPa (e.g., about 25 MPa to about 75 MPa, about 25 MPa to about 70 MPa, about 25 MPa to about 65 MPa, about 45 MPa to about 80 MPa, about 50 MPa to about 80 MPa, or about 60 MPa to about 80 MPa).
[0076] The maximum CT 320 can be located in the range of about 0.3·t to about 0.7·t, about 0.4·t to about 0.6·t, or about 0.45·t to about 0.55·t. It should be noted that any one or more of the surface CS 310 and the maximum CT 320 can be determined by the thickness of the glass-based article. For example, a glass-based article having a thickness of about 0.8 mm can have a maximum CT of about 75 MPa or less. As the thickness of the glass-based article decreases, the maximum CT can increase. In other words, the maximum CT increases with decreasing thickness (i.e., as the glass-based article becomes thinner).
[0077] In some embodiments, the ratio of maximum CT320 to surface CS310 is in the range of about 0.01 to about 0.2 (e.g., in the range of about 0.01 to about 0.18, about 0.01 to about 0.16, about 0.01 to about 0.15, about 0.01 to about 0.14, about 0.01 to about 0.1, about 0.02 to about 0.2, about 0.04 to about 0.2, about 0.05 to about 0.2, about 0.06 to about 0.2, about 0.08 to about 0.2, about 0.1 to about 0.2, or about 0.12 to about 0.2). In known chemically strengthened glass-based articles, the ratio of maximum CT320 to the absolute value of surface CS310 is 0.2 or less or about 0.15 or less. In some embodiments, the absolute value of surface CS can be 1.5 times (or 2 times or 2.5 times) or more of maximum CT. In some embodiments, the absolute value of surface CS can be up to about 48 times the maximum CT, up to about 40 times the maximum CT, up to about 20 times the maximum CT, up to about 10 times the maximum CT, or up to about 8 times the maximum CT. The absolute value of surface CS can be in the range of up to about 5 times to about 50 times the CT.
[0078] In one or more embodiments, the stress profile 312 includes a maximum CS, typically a surface CS 310, which may be found at one or both of the first surface 302 and the second surface 304. In one or more embodiments, the CS layer or region 315 extends through a portion of the thickness along the DOC 317 and the maximum CT 320. In one or more embodiments, the DOC 317 may be about 0.1·t or greater. For example, the DOC 317 may be about 0.12·t or greater, about 0.14·t or greater, about 0.15·t or greater, about 0.16·t or greater, 0.17·t or greater, 0.18·t or greater, 0.19·t or greater, 0.20·t or greater, about 0.21·t or greater, or up to about 0.25·t. In some embodiments, the DOC 317 is less than the chemical depth 342. Chemical depth 342 can be about 0.4·t or more, 0.5·t or more, about .55·t or more, or about 0.6·t or more. In one or more embodiments, stress profile 312 can be described as a parabolic shape. In some embodiments, the stress profile along a region or depth of the glass-based article exhibiting tensile stress exhibits a parabolic shape. In one or more particular embodiments, stress profile 312 does not include any portion that exhibits a flat stress (i.e., compressive or tensile) or a substantially constant stress (i.e., compressive or tensile). In some embodiments, the CT region exhibits a stress profile that is substantially free of flat stress or substantially constant stress. In one or more embodiments, all points of stress profile 312 between a thickness range of about 0·t up to about 0.2·t and greater than 0.8·t (or about 0·t up to about 0.3·t and greater than 0.7·t) include a tangent that has a slope less than about -0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer. In some embodiments, the slope may be less than about -0.2 MPa / micrometer or greater than about 0.2 MPa / micrometer. In some specific embodiments, the slope may be less than about -0.3 MPa / micrometer or greater than about 0.3 MPa / micrometer. In further specific embodiments, the slope may be less than about -0.5 MPa / micrometer or greater than about 0.5 MPa / micrometer.In other words, the stress profiles of one or more embodiments along these thickness ranges (i.e., from 0·t up to about 0.2·t and greater than 0.8·t, or from about 0·t to about 0.3·t and 0.7·t or greater) exclude points having a tangent with a slope as described herein. Without being bound by theory, known error functions or quasi-linear stress profiles have points along these thickness ranges (i.e., from about 0·t up to about 0.2·t and greater than 0.8·t, or from about 0·t to about 0.3·t and 0.7·t or greater) having a tangent with a slope that is in the range of about -0.1 MPa / micrometer to about 0.1 MPa / micrometer (exhibiting a flat or zero slope stress profile along such thickness ranges, as shown at 220 in FIG. 2). The glass-based articles of one or more embodiments of the present disclosure do not exhibit such stress profiles having a flat or zero slope stress profile along these thickness ranges, as shown in FIG. 3.
[0079] In one or more embodiments, the glass-based article exhibits a stress profile within a thickness range of about 0.1·t to 0.3·t and about 0.7·t to 0.9·t, including a tangent line with a maximum slope and a tangent line with a minimum slope. In some cases, the difference between the maximum slope and the minimum slope is about 3.5 MPa / micrometer or less, about 3 MPa / micrometer or less, about 2.5 MPa / micrometer or less, or about 2 MPa / micrometer or less. In another embodiment, the thickness range in which the difference between the maximum slope and the minimum slope falls within the above range includes up to about 0.02·t and more than 0.980·t, such as up to about 0.0250·t and more than 0.9750·t, or up to about 0.0275·t and more than 0.9725·t, or up to about 0.030·t and more than 0.970·t, or up to about 0.0350·t and more than 0.9650·t.
[0080] In one or more embodiments, the glass-based article includes a stress profile 312 that is substantially free of any flat portion extending in a depth direction, or along at least a portion of the thickness t of the glass-based article. In other words, the stress profile 312 increases or decreases substantially continuously along the thickness t. In some embodiments, the stress profile is substantially free of any flat portion in a depth direction having a length of about 10 micrometers or more, about 50 micrometers or more, or about 100 micrometers or more, or about 200 micrometers or more. As used herein, the term "flat" refers to a slope along a flat portion having a magnitude of less than about .5 MPa / micrometer, or less than about .2 MPa / micrometer. In some embodiments, one or more portions of the stress profile that are substantially free of flat portions in a depth direction are present at a depth in the glass-based article of about 5 micrometers or more (e.g., 10 micrometers or more, or 15 micrometers or more) from either or both of the first surface or the second surface. For example, along a depth of about 0 micrometers to less than about 5 micrometers from the first surface, the stress profile can include a straight line portion, while at a depth of about 5 micrometers or more from the first surface, the stress profile can be substantially free of flat portions. As used herein, "straight line" includes line segments that have a flat slope and line segments that do not have a flat slope, an example of the latter being seen in FIG. 6 within a depth of about 12 micrometers from the surface.
[0081] In some embodiments, the stress profile can include a linear portion from a depth of about 0t up to about 0.1t, and can be substantially free of a flat portion from a depth of about 0.1t to about 0.4t. In some embodiments, the stress profile from a thickness in the range of about 0t to about 0.1t can have a slope in the range of about 20 MPa / micrometer to about 200 MPa / micrometer. As described herein, such embodiments can be formed using one ion exchange process, or multiple (e.g., two or more) ion exchange processes, where the bath includes two or more alkali salts or is a mixed alkali salt bath.
[0082] In one or more embodiments, the glass-based article can be described in terms of the shape of the stress profile along the CT region (327 in FIG. 3). For example, in some embodiments, the stress profile along the CT region (where the stress becomes tensile) can be approximated by the formula: In some embodiments, the stress profile along the CT region can be approximated by Equation (1): Stress(x)=MaxCT-(((MaxCT·(n+1)) / 0.5 n )·|(x / t)-0.5| n ) (1) In equation (1), Stress(x) is the stress value at location x, where Stress is positive (tension). MaxCT is the maximum central tension as a positive value in MPa. The value x is the location along the thickness (t) ranging from 0 to t, where x=0 is at one surface (302 in FIG. 3), x=0.5t is the center of the glass-based article, and Stress(x)=MaxCT where x=t is at the opposing surface (304 in FIG. 3). The MaxCT used in equation (1) can be in the range of about 50 MPa to about 80 MPa (e.g., about 60 MPa to about 80 MPa, about 70 MPa to about 80 MPa, about 50 MPa to about 75 MPa, about 50 MPa to about 70 MPa, or about 50 MPa to about 65 MPa), and n is a fitting parameter from 1.5 to 5 (e.g., 2 to 4, 2 to 3, or 1.8 to 2.2), whereby for n=2 a parabolic stress profile can be obtained, and exponents deviating from n=2 result in a stress profile with a nearly parabolic stress profile.
[0083] In some embodiments, the stress profile can be tailored by heat treatment. In such embodiments, heat treatment can be performed before any ion exchange process, during the ion exchange process, or after all ion exchange processes. In some embodiments, heat treatment can reduce the slope of the stress profile at or near the surface. In some embodiments, if a steeper slope, i.e., a larger slope, is desired at the surface, an ion exchange process after heat treatment can be utilized to obtain a "spike" or increase the slope of the stress profile at or near the surface.
[0084] In one or more embodiments, the stress profile 312 (and / or the estimated stress profile 340) is obtained by a non-zero concentration of metal oxide that varies along a portion of the thickness, for example, about 10 micrometers, 100 micrometers, or the entire thickness. The concentration variation may be described herein as a gradient. In some embodiments, the concentration of the metal oxide is non-zero and varies along a thickness range of about 0·t to about 0.3·t. In some embodiments, the concentration of the metal oxide is non-zero and varies along a thickness range of about 0·t to about 0.35·t, about 0·t to about 0.4·t, about 0·t to about 0.45·t, or about 0·t to about 0.48·t. The metal oxide may be described as generating stress in the glass-based article. The concentration variation may be continuous along the aforementioned thickness range. The concentration variation may include a change in metal oxide concentration of about 0.2 mol % along a thickness portion of about 100 micrometers. This change can be measured by methods known in the art, such as a microprobe as shown in Example 1. Metal oxides that have a non-zero concentration and vary along a portion of the thickness can be described as generating stress in the glass-based article.
[0085] The variation in concentration can be continuous along the aforementioned thickness range. In some embodiments, the variation in concentration can be continuous along a thickness portion in the range of about 10 micrometers to about 30 micrometers. In some embodiments, the concentration of the metal oxide decreases from a value at the first surface to a point between the first surface and the second surface, and increases from that value to the second surface.
[0086] The concentration of metal oxides can include two or more metal oxides (e.g., a combination of Na2O and KO). In some embodiments, when two metal oxides are used and the radii of the ions are different from one another, at shallow depths, the concentration of the ions with the larger radius is higher than the concentration of the ions with the smaller radius, while at deeper depths, the concentration of the ions with the smaller radius is higher than the concentration of the ions with the larger radius. For example, when one bath containing Na and K is used for the ion exchange process, at shallower depths, the concentration of K+ ions is higher than the concentration of Na+ ions in the glass-based article, while at deeper depths, the concentration of Na+ is higher than the concentration of K+ ions. This is due in part to the size of the ions. In such glass-based articles, the surface or near-surface regions contain larger CS due to the higher amount of larger ions (i.e., K+ ions) at or near the surface. This larger CS can be indicated by a stress profile with a steeper slope at or near the surface (i.e., a spike in the stress profile at the surface).
[0087] The concentration gradient or variation of one or more metal oxides is produced by chemical strengthening of the glass-based substrate as described herein above, in which a plurality of first metal ions in the glass-based substrate are exchanged with a plurality of second metal ions. The first ions can be ions of lithium, sodium, potassium, and rubidium. The second metal ions can be one of sodium, potassium, rubidium, and cesium, with the proviso that the second alkali metal ion has an ionic radius larger than the ionic radius of the first alkali metal ion. The second metal ion is present in the glass-based substrate as its oxide (e.g., Na2O, KO, Rb2O, Cs2O, or a combination thereof).
[0088] In one or more embodiments, the concentration gradient of the metal oxide extends along a substantial portion of or the entire thickness t of the glass-based article including the CT layer 327. In one or more embodiments, the concentration of the metal oxide is about 0.5 mol % or greater in the CT layer 327. In some embodiments, the concentration of the metal oxide may be about 0.5 mol % or greater (e.g., about 1 mol % or greater) along the entire thickness of the glass-based article, being highest at the first surface 302 and / or the second surface 304, and continuing to decrease substantially to a value at a point between the first surface 302 and the second surface 304. At that point, the concentration of the metal oxide is lowest along the entire thickness t, but the concentration at that point is also non-zero. In other words, the non-zero concentration of that particular metal oxide extends along a substantial portion of or the entire thickness t (as described herein). In some embodiments, the lowest concentration of the particular metal oxide is present in the CT layer 327. The total concentration of the particular metal oxide in the glass-based article may be in the range of about 1 mol % to about 20 mol %.
[0089] In one or more embodiments, the glass-based article includes a first metal oxide concentration and a second metal oxide concentration, where the first metal oxide concentration is in a range of about 0 mol% to about 15 mol% along a first thickness range of about 0t to about 0.5t, and the second metal oxide concentration is in a range of about 0 mol% to about 10 mol% from a second thickness range of about 0 micrometers to about 25 micrometers (or about 0 micrometers to about 12 micrometers), but the concentration of one or both of the first metal oxide and the second metal oxide is non-zero along a substantial portion or the entire thickness of the glass-based article. The glass-based article can include an optional third metal oxide concentration. The first metal oxide can include Na2O, while the second metal oxide can include KO.
[0090] The concentration of a metal oxide can be determined from a baseline amount of the metal oxide in the glass-based article before it is adjusted to include a concentration gradient of such metal oxide.
[0091] In one or more embodiments, glass-based articles can be described in terms of how they break and the fragments resulting from such breakage. In one or more embodiments, upon breaking, the glass-based article breaks into 2 or more fragments per square inch (or per 6.4516 square centimeters) of the glass-based article (before breaking), where the sample size used was a 2 inch by 2 inch square. In some cases, the glass-based article breaks into 3 or more, 4 or more, 5 or more, or 10 or more fragments per square inch (or per 6.4516 square centimeters) of the glass-based article (before breaking), where the sample size used was a 2 inch by 2 inch square. In some cases, upon breaking, the glass-based article breaks into fragments such that 50% or more of the fragments have a surface area of less than 5%, less than 2%, or less than 1% of the surface area of the glass-based article (before breaking). In some embodiments, upon breaking, the glass-based article breaks into fragments such that 90% or more, or even 100% of the fragments have a surface area less than 5%, less than 2%, or less than 1% of the surface area of the glass-based article (before breaking).
[0092] In one or more embodiments, after chemical strengthening of the glass-based article, the resulting stress profile 317 (and estimated stress profile 340) of the glass-based article provides improved fracture resistance. For example, in some embodiments, after fracture, the glass-based article includes fragments having an average maximum cross-sectional dimension of about 0.2·t or less (e.g., 1.8·t, 1.6·t, 1.5·t, 1.4·t, 1.2·t, or 1.·t or less).
[0093] In one or more embodiments, the glass-based article has a compressibility of about 0.7 MPa m 1 / 2 Fracture toughness (K 1C In some cases, the fracture toughness is about 0.8 MPa m 1 / 2 or above or approximately 0.9MPa m 1 / 2 In some embodiments, the fracture toughness is about 0.7 MPa m 1 / 2 ~Approx. 1MPa m 1 / 2The fracture toughness values (K 1C ) was calculated by using Equation 5 of Bubsey, RT et al., “Closed-Form Expressions for Crack-Mouth Displacement and Stress Intensity Factors for Chevron-Notched Short Bar and Short Rod Specimens Based on Experimental Compliance Measurements,” NASA Technical Memorandum 83796, pp. 1-30 (October 1992) * m is calculated, the values are those measured by the chevron-notched short bar (CNSB) method disclosed in Reddy, KPR et al., “Fracture Toughness Measurement of Glass and Ceramic Materials Using Chevron-Notched Specimens,” J. Am. Ceram. Soc., 71[6], C-310-C-313 (1988).
[0094] In some embodiments, the substrate may also be characterized as having a hardness of about 500 HVN to about 800 HVN as measured by the Vickers Hardness Test at a load of 200 g.
[0095] The glass-based articles described herein have a thermal conductivity of 0 J / m 2 Super ~ about 20J / m 2 In some cases, the stored tensile energy can be in the range of about 1 J / m 2 ~about 20J / m 2 , about 2J / m 2 ~about 20J / m 2 , about 3J / m 2 ~about 20J / m 2 , about 4J / m 2 ~about 20J / m 2 , about 1J / m 2 ~About 19J / m 2 , about 1J / m2 ~about 18J / m 2 , about 1J / m 2 ~about 16J / m 2 , about 4J / m 2 ~about 20J / m 2 , or about 4 J / m 2 ~about 18J / m 2 The stored tensile energy can be in the range of: Stored tensile energy (J / m 2 )=[(1-ν) / E]∫(σ^2)(dt) (2) where v is Poisson's ratio, E is Young's modulus (in MPa), σ is stress (in MPa), and the integral is calculated over the thickness (in micrometers) of the tensile region only.
[0096] The glass-based articles described herein generally have an elastic modulus or Young's modulus of less than about 80 GPa. The elastic modulus, which is inherent to the composition of the glass-based article, can impart the desired high hardness, which is an extrinsic property, to the final glass-based article produced therefrom. For clarity, unless a specific type of elastic modulus measurement is specified, the elastic modulus described herein is the Young's modulus of the material, rather than, for example, shear modulus, bulk modulus, Poisson's ratio, etc.
[0097] In some embodiments, the glass-based article comprises a high liquidus viscosity that allows the glass-based article to be formed by down-draw techniques (e.g., fusion draw, slot draw, and other similar methods) that can obtain high precision surface smoothness. As used herein, the term "liquidus viscosity" refers to the viscosity of molten glass at the liquidus temperature, where the term "liquidus temperature" refers to the temperature at which crystals first appear when molten glass is cooled from the melting temperature (or the temperature at which crystals last melt when the temperature is increased from room temperature). The liquidus viscosity is determined by the following method. First, the liquidus temperature of the glass is measured according to ASTM C829-81 (2015) entitled "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method". Second, the viscosity of the glass at the liquidus temperature is measured according to ASTM C965-96 (2012) entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point". Generally, the glass-based articles described herein (or compositions used to form such articles) exhibit a liquidus viscosity of about 100 kilopoise (kP) (10 kPa·s) or greater. Where a higher liquidus viscosity is desired for downdraw processability, the glass-based articles (or compositions used to form such articles) exhibit a liquidus viscosity of 200 kP (20 kPa·s) or greater (e.g., about 600 kP (60 kPa·s) or greater).
[0098] In one or more embodiments, the glass-based article exhibits a Knoop Lateral Cracking Scratch Threshold in the range of about 4N to about 7N, about 4.5N to about 7N, about 5N to about 7N, about 4N to about 6.5N, about 4N to about 6N, or about 5N to about 6N. As used herein, the Knoop Lateral Cracking Scratch Threshold is the initiation of a lateral crack that extends more than twice the width of the microductile scratch groove formed with the Knoop indenter (3 or more out of 5 indentation events). In some embodiments, the Knoop Lateral Cracking Scratch Threshold may be in the range of about 10 to about 16 Newtons. As used herein, the Knoop Lateral Cracking Scratch Threshold is the initiation of a lateral crack that extends more than twice the width of the microductile scratch groove formed with the Knoop indenter (3 or more out of 5 indentation events). A series of increasing constant load scratches (minimum three at each load, but more at each load can be used to increase the confidence level) are performed to determine the Knoop scratch threshold. In the Knoop scratch side crack threshold test, at each load, the glass substrate and / or article sample is scratched with a Knoop indenter over a length of 10 mm at a speed of 0.25 mm / s. The Knoop scratch threshold range can be determined by comparing the test specimen to one of three failure types: 1) a persistent side crack more than twice the width of the groove, 2) the presence of a side crack less than twice the width of the groove with damage contained within the groove, and damage visible to the naked eye, or 3) the presence of a large subsurface side crack more than twice the width of the groove and / or a central crack at the apex of the scratch. The scratch threshold is then the maximum load at which no failure occurs in three or more of the five events.
[0099] In one or more embodiments, the glass-based article exhibits a Vickers indentation fracture threshold in the range of about 10 kgf (about 98 N) or more, about 12 kgf (about 118 N) or more, or about 15 kgf (about 147 N) or more. As used herein, the indentation fracture threshold (or Vickers crack initiation threshold) was measured by a Vickers indenter. The Vickers indentation fracture threshold is a measure of the indentation damage resistance of glass. This test involved the use of a square-based pyramidal diamond indenter with a face-to-face angle of 136°, called a Vickers indenter. This Vickers indenter was the same as that used in standard microhardness testing (reference ASTM-E384-11). A minimum of five specimens were selected to represent the type and / or family of glass of interest. For each specimen, multiple sets of five indentations were introduced on the specimen surface. Each set of five indentations was introduced at a specific load, with each individual indentation being a minimum of 5 mm apart and never closer than 5 mm to the specimen edge. An indenter load / unload rate of 50 kg / min was used for test loads ≥ 2 kg. For test loads < 2 kg, a rate of 5 kg / min was used. A dwell (i.e., hold) time of 10 seconds was used at the target load. The machine maintained load control during the dwell time. After a time of at least 12 hours, the indentations were examined under reflected light using a compound microscope at 500x magnification. The presence or absence of a central / radial crack or specimen failure was then recorded for each indentation. It should be noted that since in this test, central / radial crack formation or specimen failure was of interest, the formation of lateral cracks was not considered to be indicative of threshold behavior. The specimen threshold is defined as the midpoint of the minimum continuous indentation load lumped together at the threshold where more than 50% of the individual indentations met. For example, if in an individual specimen, two of five indentations (40%) induced by a load of 5 kg exceed the threshold and three of five indentations (60%) induced by a load of 6 kg exceed the threshold, the threshold for the specimen is defined as the midpoint between 5 kg and 6 kg, i.e., 5.5 kg. The average threshold for the specimen is defined as the arithmetic mean of the thresholds for all individual specimens. Along with the mean, the range (minimum - maximum) of the midpoints for all specimens is reported for each specimen.To minimize variability in the fatigue (stress corrosion) behavior of the glass specimens, the pre-test, test, and post-test environments were controlled at 23±2°C and 50±5% RH. Note that when initially testing an unknown composition or family, the required indentation loads and tier increments were determined by performing an "iterative survey." Once the specimen's performance is well known, subsequent testing can be streamlined by testing only at loads close to the expected threshold, and then further indentation loads can be "padded" only if necessary.
[0100] In one or more embodiments, the glass-based article exhibits improved surface strength when subjected to the Abrasion Ring-on-Ring (AROR) test. The strength of a material is defined as the stress at which fracture occurs. The AROR test is a surface strength measurement for testing flat glass specimens, and ASTM C1499-09(2013) entitled "Standard Test Method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperature" is the basis for the AROR test method described herein. The contents of ASTM C1499-09 are incorporated herein by reference in their entirety. In one embodiment, the glass specimen is abraded prior to ring-on-ring testing using 90 grit silicon carbide (SiC) particles applied to the glass specimen using the methods and apparatus described in Annex A2 entitled "abrasion Procedures" of ASTM C158-02(2012) entitled "Standard Test Methods for Strength of Glass by Flexure (Determination of Modulus of Rupture)." The contents of ASTM C158-02, and in particular the contents of Annex 2, are hereby incorporated by reference in their entirety.
[0101] Prior to ring-on-ring testing, the surface of the glass-based article is sanded as described in ASTM C158-02, Annex 2 to normalize and / or control the surface defect condition of the specimen using the apparatus shown in Figure A2.1 of ASTM C158-02. Typically, the abrasive material is sandblasted onto the surface 110 of the glass-based article at a load of 15 psi (103 kPa) using an air pressure of 304 kPa (44 psi), although in the following examples, the abrasive material was sandblasted onto the surface 110 at other loads (e.g., 25 psi (172 kPa) or 45 psi (310 kPa)). After the airflow stabilized, the surface was sandblasted at a distance of 5 cm. 3 of abrasive material was added to the funnel and the sample was sandblasted for 5 seconds after the introduction of the abrasive material.
[0102] For the AROR test, a glass-based article 410 having at least one polished surface as shown in Figure 4 is placed between two concentric rings of different sizes to determine the equibiaxial flexural strength (i.e., the maximum stress the material can withstand when subjected to bending between two concentric rings), also as shown in Figure 4. In the AROR configuration 400, the polished glass-based article 410 is supported by a support ring 420 having a diameter D2. A force F is applied by a load cell (not shown) to the surface of the glass-based article by a loading ring 430 having a diameter D1.
[0103] The ratio of the diameters of the load ring and the support ring D1 / D2 can be in the range of about 0.2 to about 0.5. In some embodiments, D1 / D2 is about 0.5. The load ring and the support ring 430, 420 should be concentrically arranged within 0.5% of the support ring diameter D2. The load cell used for testing should be accurate to within ±1% at any load within the selected range. In some embodiments, the testing is performed at a temperature of 23±2° C. and a relative humidity of 40±10%.
[0104] For the design of the fixture, h / 2≦r≦3h / 2, where r is the radius of the protruding surface of the loading ring 430, and h is the thickness of the glass-based article 410. The loading and support rings 430, 420 are typically made of hardened steel with a hardness of HRc>40. AROR fixtures are commercially available.
[0105] The intended failure mechanism of the AROR test is to observe the failure of the glass-based article 410 originating from the surface 430a within the loading ring 430. Failures occurring outside this region, i.e., between the loading ring 430 and the support ring 420, are excluded from the data analysis. However, due to the thinness and high strength of the glass-based article 410, large deflections are observed, in some cases exceeding ½ of the specimen thickness h. Thus, it is not uncommon to observe a high percentage of failures originating from below the loading ring 430. Without knowing the stress development both inside and below the ring (collected by strain gauge analysis) and the origin of failure for each specimen, the stress cannot be calculated accurately. Therefore, the AROR test focuses on the peak load at failure as the response to be measured.
[0106] The strength of glass-based articles depends on the presence of surface flaws. However, because the strength of glass is statistical in nature, it is not possible to accurately predict the likelihood of a flaw of a particular size being present. Therefore, a probability distribution can generally be used as a statistical representation of the data obtained.
[0107] In some embodiments, the glass-based articles described herein have a surface or equibiaxial flexural strength of 20 kgf (about 196 N) or more and up to about 30 kgf (about 294 N) when measured by the AROR test using a load of 25 psi (172 kPa) or even 45 psi (310 kPa) to abrade the surface. In another embodiment, the surface strength is 25 kgf or more (about 245 N), and in yet another embodiment, 30 kgf or more (about 294 N).
[0108] In some embodiments, the glass-based articles described herein can be described in terms of their performance in an inverted ball on sandpaper (IBoS) test. The IBoS test is a dynamic component-level test that mimics the primary mechanisms of damage introduction and bending fracture that typically occur in glass-based articles used in mobile or handheld electronic devices, as shown diagrammatically in FIG. 27A. In this field, damage introduction (a in FIG. 27A) is performed on the top surface of the glass-based article. Fracture initiates on the top surface of the glass-based article and either penetrates the glass-based article (b in FIG. 27A) or propagates from the bending on the top surface or from an internal portion of the glass-based article (c in FIG. 27A). The IBoS test is designed to simultaneously introduce damage to the surface of the glass and apply bending under dynamic load. In some cases, glass-based articles show improved drop performance when they contain compressive stresses than when the same glass-based article does not contain compressive stresses.
[0109] The IBoS test apparatus is shown diagrammatically in FIG. 27B. The apparatus 500 includes a test stand 510 and a ball 530. The ball 530 is a rigid or solid ball, such as, for example, a stainless steel ball. In one embodiment, the ball 530 is a 4.2 gram stainless steel ball with a diameter of 10 mm. The ball 530 is dropped directly onto the glass-based article sample 518 from a predetermined height h. The test stand 510 includes a solid base 512 including a hard rigid material, such as granite. A sheet 514 having an abrasive material disposed on its surface is placed on the top surface of the solid base 512 with the surface having the abrasive material facing upward. The sheet 514 is an abrasive paper having a 30 grit surface in some embodiments and a 180 grit surface in other embodiments. The glass-based article sample 518 is maintained on the sheet 514 by a sample holder 515 such that there is an air gap 516 between the glass-based article sample 518 and the sheet 514. The gap 516 between the sheet 514 and the glass-based article sample 518 allows the glass-based article sample 518 to bend upon impact with the ball 530 up to the polished surface of the sheet 514. In one embodiment, the glass-based article sample 218 is clamped across all corners to keep the bending contained only at the point of impact of the ball, ensuring repeatability. In some embodiments, the sample holder 515 and test stand 510 are adapted to accommodate sample thicknesses up to about 2 mm. The gap 516 is in the range of about 50 μm to about 100 μm. The gap 516 is adapted to adjust for differences in material stiffness (Young's modulus, Emod), but also includes the elastic modulus and thickness of the sample. An adhesive tape 520 can be used to cover the top surface of the glass-based article sample to collect debris during a breakage event of the glass-based article sample 518 upon impact of the ball 530.
[0110] Various materials can be used as the abrasive surface. In a particular embodiment, the abrasive surface can be abrasive paper, such as silicon carbide or alumina abrasive paper, industrial abrasive paper, or any abrasive material known to those skilled in the art as having a similar hardness and / or sharpness. In some embodiments, abrasive paper with 30 grit can be used, since it has a more uniform surface topology than either concrete or asphalt, and has a grit size and sharpness that causes the desired level of damage to the specimen surface.
[0111] In one aspect, a method 600 of performing an IBoS test using the apparatus 500 previously described herein is shown in FIG. 28. In step 610, a glass-based article sample (218 in FIG. 36) is placed in the previously described test stand 510 and secured in a sample holder 515 such that a gap 516 is formed between the glass-based article sample 518 and a sheet 514 having an abrasive surface. The method 600 assumes that the sheet 514 having an abrasive surface is already placed in the test stand 510. However, in some embodiments, the method can include placing the sheet 514 in the test stand 510 such that the surface having the abrasive material faces upward. In some embodiments (step 610a), an adhesive tape 520 is attached to the top surface of the glass-based article sample 518 prior to securing the glass-based article sample 518 in the sample holder 510.
[0112] In step 620, a solid sphere 530 of a predetermined mass and size is dropped from a predetermined height h onto the top surface of the glass-based article sample 518 such that the sphere 530 impacts the top surface (or the adhesive tape 520 applied to the top surface) at approximately the center of the top surface (i.e., within 1 mm, or within 3 mm, or within 5 mm, or within 10 mm of the center). After impact in step 620, the extent of damage to the glass-based article sample 518 is measured (step 630). As previously described herein, the term "fracture" is used herein to mean the propagation of a crack through the entire thickness and / or surface of a substrate when the substrate is dropped or struck by an object.
[0113] In method 600, the sheet 518 having an abrasive surface can be replaced after each drop to avoid the "aging" effect that has been observed when repeatedly using drop test surfaces of other types (e.g., concrete or asphalt).
[0114] Typically, various pre-determined drop heights h and increments are used in method 600. The test can, for example, use a minimum drop height (e.g., about 10-20 cm) to begin. The height can then be increased for successive drops, either by a set increment or by a variable increment. The test described in method 600 is stopped when the glass-based article sample 518 breaks or fractures (step 631). Alternatively, the drop test of method 600 can be stopped if the drop height h reaches a maximum drop height (e.g., about 100 cm) without fracture, or step 620 can be repeated at the maximum height until fracture occurs.
[0115] In some embodiments, the IBoS test of method 600 is performed only once for each glass-based article sample 518 at each predetermined height h, however, in other embodiments, each sample may be tested multiple times at each height.
[0116] If failure of the glass-based article specimen 518 occurs (step 631 in FIG. 28), IBoS testing according to method 600 is terminated (step 640). If no failure is observed when the ball is dropped at a predetermined drop height (step 632), the drop height is increased by a predetermined increment, e.g., 5, 10, or 20 cm (step 634), and steps 620 and 630 are repeated until either specimen failure is observed (631) or the specimen reaches the maximum test height without failure (636). Testing according to method 600 is terminated when step 631 or 636 is reached.
[0117] When performing the aforementioned inverted ball on abrasive paper (IBoS) test, the glass-based article embodiments described herein have a survival rate of about 60% or more when a ball is dropped onto the surface of the glass from a height of 100 cm. For example, a glass-based article is described as having a survival rate of 60% when dropped from a particular height if three out of five identical (or nearly identical) samples (i.e., having nearly the same composition and, when tempered as described herein, having nearly the same compressive stress and compressive or compressive stress layer depth) survive the IBoS drop test without breaking when dropped from a specified height (in this case 100 cm). In another embodiment, the survival rate of the tempered glass-based article in the 100 cm IBoS test is about 70% or more, in another embodiment about 80% or more, and in yet another embodiment about 90% or more. In another embodiment, the survival rate of the tempered glass-based article dropped from a height of 100 cm in the IBoS test is about 60% or more, in another embodiment about 70% or more, in yet another embodiment about 80% or more, and in another embodiment about 90% or more. In one or more embodiments, the survival rate of the reinforced glass-based articles dropped from a height of 150 cm in the IBoS test is about 60% or more, in other embodiments about 70% or more, in yet other embodiments about 80% or more, and in other embodiments about 90% or more.
[0118] To determine the survival rate of a glass-based article when dropped from a predetermined height using the IBoS test method and apparatus described hereinabove, at least five identical (or nearly identical) specimens of the glass-based article (i.e., having nearly the same composition and, if reinforced, having nearly the same compressive stress and compression or depth of layer) are tested, although a greater number of specimens (e.g., 10, 20, 30, etc.) can be tested to increase the confidence level of the test results. Each specimen is dropped once from a predetermined height (e.g., 100 cm or 150 cm), or alternatively, dropped from progressively higher heights without failure until the predetermined height is reached, and visually (i.e., with the naked eye) examined for evidence of failure (crack formation and propagation through the thickness and / or surface of the specimen). If no failure is observed after dropping from the predetermined height, the specimen is considered to have "survived" the drop test, and if failure is observed when the specimen is dropped from a height equal to or less than the predetermined height, the specimen is considered to have "failed" (or "did not survive"). Survival is determined as the percentage of a group of samples that survive the drop test. For example, if 7 samples out of a group of 10 do not break when dropped from a predetermined height, the survival rate of the glass is 70%.
[0119] 29-33, there is shown one embodiment of an apparatus 1100 for alternative impact testing of brittle substrates, which is used to perform "impact threshold testing" of the main surface of the specimen and the edge of the specimen. The apparatus 1100 includes a pendulum 1102 including a weight 1104 attached to a pivot 1106. The weight on the pendulum is a weight that is suspended from the pivot and connected to the pivot by an arm. Thus, the weight 1104 shown in the figures is connected to the pivot 1106 by an arm 1108, which may be in the form of a string, or a rod, or multiple rods, such as two rods as shown. As best shown in FIG. 33, the weight 1104 has an equilibrium position 1105, shown by the dashed line, where the angle β is zero. In other words, the arm 1108 is not in a raised position.
[0120] The weight 1104 includes a base 1110 for receiving a brittle substrate. As shown in more detail in FIG. 34, the base 1110 for receiving a brittle substrate 1112 has two ends 1114, 1116, an inner surface 1113, and an outer surface 1115. The base 1110 has a first end 1120 and a second end 1122, and a curved surface 1124 that defines a radius of curvature between the first end 1120 and the second end 1122. A suitable material for the base 1110 is metal. The curved surface 1124 has an apex 1125.
[0121] The apparatus 1100 according to one or more embodiments further includes a first fixture 1130 and a second fixture 1132 for holding two ends 1114, 1116 of the brittle substrate 1112 and applying a force to bend the brittle substrate 1112 about the curved surface 1124, causing the brittle substrate to conform to its radius of curvature. By bending the brittle substrate 1112, the brittle substrate has an apex 1127 that conforms to the apex 1125 of the curved surface 1124. In one or more particular embodiments, the curvature of the curved surface 1124 and the brittle substrate 1112 can have a constant radius or a compound radius. Each of the first fixture 1130 and the second fixture 1132 is a clamp, a toggle clamp as shown in FIG.
[0122] The apparatus 1100 further includes a roughened surface, which is an abrasive sheet having an abrasive surface that is positioned to contact the outer surface 1115 of the substrate 1112 (or corners 3501, 3503, etc., as shown in FIG. 35). The abrasive sheet is attached with double-sided tape to the impact surface 1150 (of the impact object 1140 described below) such that the abrasive surface of the abrasive sheet faces the curved surface 1124 on which the substrate 1112 is mounted. One suitable abrasive sheet is Indasa Rhynowet® Plus Line P180 grit abrasive paper. The abrasive paper according to one or more embodiments is cut into 25 mm square pieces, and the abrasive paper is flattened if the pieces bend during the cutting process.
[0123] The apparatus 1100 further includes an impacting object 1140 positioned such that when the weight 1104 is released from a position at an angle β greater than zero from the equilibrium position 1105, the curved surface 1124 of the weight 1104 (or the substrate 1112 mounted on the curved surface 1124) contacts the impact surface 1150 of the impacting object 1140 (or the abrasive side of an abrasive sheet disposed on the impact surface 1150). In the illustrated embodiment, the impacting object 1140 is an L-shaped bracket attached to a base 1142, which is attached to the base 1142 by a screw 1144. The impacting object 1140 can also be attached by any other suitable mechanism, such as a bolt, a rivet, a clamp, etc. The base 1142 includes a stopper 1146 that allows the apparatus 1100 to be held at the end of a work base 1148. In the illustrated embodiment, the impact object 1140 is fixed and does not move when the weight 1104 contacts the impact object 1140 at the impact surface 1150. The impact surface 1150 can be a separate element that is movable in the xy plane in a slot 1152 as best shown in FIG. 32. Alternatively, the impact surface 1150 need not move relative to the impact object 1140. In one or more embodiments, the weight 1104 and base 1110 are sized and shaped such that when the brittle substrate is attached to the base 1110 and the weight 1104 is released from a position at an angle β greater than zero from the equilibrium position 1105, the brittle substrate 1112 experiences a bending radius and impact force that mimics the bending radius of the chemically strengthened cover glass of a mobile phone or tablet device when a user of the mobile phone or tablet device drops the mobile phone or tablet device to the ground.
[0124] In one or more embodiments, the radius of curvature of the curved surface 1124 on the pedestal 1110 is selected to provide a bending tensile force of 100 MPa when the substrate is bent around the curved surface 1124, such that this tensile force is an externally applied tensile force resulting from the stress of bending the substrate. Thus, when the substrate is bent, the tensile force is present at the apex 1125 of the brittle substrate. According to one or more embodiments, the radius of curvature is in the range of 0.25 m to 1.5 m, such as in the range of 0.5 m to 1 m.
[0125] In one or more embodiments, the first fixture 1130 and the second fixture 1132 are spaced apart by a distance that is the length of the cover glass of the mobile phone or tablet. In certain embodiments, the first fixture 1130 and the second fixture 1132 are spaced apart by a distance that is in the range of 50 mm to 500 mm.
[0126] Another aspect of the present disclosure relates to a method for impact testing a brittle sheet, the surface impact threshold test method comprising: bending a brittle sheet having a contact surface to obtain a curved sheet having a radius of curvature and a vertex on the contact surface; and using a pendulum to impact an impacting object on the vertex of the curved sheet. In one embodiment, the curved sheet is attached to a pendulum weight. In one embodiment, the curved sheet attached to the pendulum weight is positioned such that the impacting object contacts the vertex of the contact surface. In one or more embodiments, the brittle sheet is glass, and the radius of curvature is within a range that mimics the bending radius of a chemically or thermally strengthened cover glass of a mobile phone or tablet device when a user of the mobile phone or tablet device drops the mobile phone or tablet device on the ground, the drop event being such that the edge of the device contacts the ground first (as opposed to a face first drop where the device impacts the ground generally with an orientation such that the contact surface is approximately parallel to the ground). At least five identical (or nearly identical) specimens of the glass-based article (i.e., having approximately the same composition and, when tempered, having approximately the same compressive stress and compression or depth of layer) are tested, although a greater number (e.g., 10, 20, 30, etc.) of specimens can be tested to increase the confidence level of the test results.
[0127] In one or more embodiments, an abrasive sheet is placed on the impact surface 1150 in a position such that the swinging motion of the arm 1108 contacts the apex of the brittle sheet. In one or more embodiments, the brittle sheet is secured to the impact object with double-sided tape.
[0128] Another embodiment is a method for crash testing a brittle sheet, the method comprising the steps of attaching the brittle sheet to a pendulum weight such that a contact surface on the brittle sheet is exposed, and moving the pendulum weight with the brittle sheet attached to the pendulum weight to contact the contact surface with an impact object. In one embodiment, the method comprises bending the brittle sheet to obtain a curved sheet with a radius of curvature and an apex on the contact surface. In one embodiment, the curved sheet attached to the pendulum weight is positioned such that the impact object contacts the apex of the contact surface. In one or more embodiments, the brittle sheet is glass, and the radius of curvature is within a range that mimics the bending radius of a chemically or thermally strengthened cover glass of a mobile phone or tablet device when a user of the mobile phone or tablet device drops the mobile phone or tablet device onto the ground, the drop event being such that the edge of the device contacts the ground first (as opposed to a face first drop where the device impacts the ground generally with an orientation such that the contact surface is approximately parallel to the ground). In some embodiments, the frangible sheet is secured to the curved surface before the apex impacts the impact object.
[0129] 29 and 30, certain non-limiting details of the operation of the apparatus include a pointer notch 1200 on the pivot 1106 that can point to various test positions 1202, i.e., positions where the arm 1108 is disposed at an angle β relative to the equilibrium position 1105 and where the pendulum motion begins. The pointer notch 1200 allows for alignment with various test positions 1202, which can be any suitable number of test positions, e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, etc., up to 50 or more. The apparatus 1100 can further include a lock, which can be in the form of a nut 1204 for fixing the arm 1108 in a desired rotational orientation relative to its central longitudinal axis, such that the base 1110 is perpendicular to the impact surface 1150 of the impact object 1140.
[0130] The device 1100 simulates a real phone drop event according to one or more embodiments. TIFF0007645327000001.tif9114
[0131] is the formula E=mgL{1-cosβ}
[0132]
number
[0133] is obtained by
[0134] where m=mass of the pendulum 1102 (including the swing arm 1108, the weight 1104, and the base 1110), L=length of the arm, g=acceleration of gravity, vf is the initial impact velocity (i.e., the velocity at which the glass first contacts the impact surface 1150 of the impacting object 1140), vi is the final impact velocity (i.e., the velocity at which the glass leaves the impact surface 1150 of the impacting object 1140, or in other words, the velocity at which the glass first leaves the impact surface 1150 of the impacting object 1140), and Δt=contact interaction time (i.e., the time during which the glass is in contact with the impact surface 1150 of the impacting object 1140). The contact interaction time is measured by a high-speed video camera, observing the number of frames during which the glass is in contact with the impact surface 1150, and multiplying it by the number of frames the high-speed video camera takes per unit time. The average force formula is useful in the case of a specimen that is not yet broken, i.e., a specimen that is mounted on the apparatus 1100 prior to testing is a specimen that is not yet broken. If the mass and length of the swing arm are known and the angle β is set at a selected position, the impact force can be calculated and used to simulate the impact on the device when dropped from a particular height. For example, the average force experienced by a substrate cover glass on a 130g mobile phone device when dropped from a height of 1 meter is calculated to be 800N. Using the mass, arm length, and angle β, this force can be replicated using the apparatus 1110 shown in Figures 29-34.
[0135] Alternatively, as shown in FIG. 35, the weight 1104 can be repositioned so that the impact object can impact the edge of the substrate 1112 with the edge impact threshold test. In this case, the impact surface 1150 of the impact object 1140 is not raised, but simply resides in a planar position where the impact object 1140 faces the weight 1104. In this orientation, the corner 3501 of the substrate 1112 contacts the impact object 1140 to which the abrasive sheet is attached in the same manner as described above. For example, this orientation mimics a drop onto the edge of an electronic device, whereby the impact energy that the substrate edge can withstand is then determined in the same manner as described above. For edge testing, the substrate 1112 is tested only once at each corner, with the top of the substrate edge being the impact point with the impact object 1140. The corner 3501 is tested first, followed by the opposite corner 3503 at pendulum heights of increasing heights. To avoid cumulative damage introduction, no more than one impact test is performed at the same location on the specimen. At least five identical (or nearly identical) specimens of the glass-based article (i.e., having approximately the same composition and, if reinforced, approximately the same compressive stress and compression or depth of layer) are tested, although a greater number (e.g., 10, 20, 30, etc.) of specimens can be tested to increase the confidence level of the test results.
[0136] The glass-based articles described herein can be transparent. In one or more embodiments, the glass-based articles can have a thickness of about 1 millimeter or less and can exhibit a transmission of about 88% or greater over wavelengths in the range of about 380 nm to about 780 nm.
[0137] The glass-based article can exhibit a substantially white color. For example, the glass-based article can exhibit an L of about 88 or more under CIE illuminant F02. * Value, a in the range of about -3 to about +3 * value, and b in the range of about -6 to about +6 * The CIELAB color space coordinates of the value can be indicated.
[0138] The choice of substrate is not particularly limited. In some examples, the glass-based article can be described as having a high cation diffusivity in the case of ion exchange. In one or more embodiments, the glass or glass ceramic has a fast ion exchange capability, i.e., a diffusion rate of 500 μm or more. 2 / hour or 450μm at 460℃ 2 / It can be characterized as exceeding time.
[0139] At a certain temperature, the diffusivity is given by Equation (4): Diffusion rate = DOL^2 / 5.6×T (4) where DOL is the depth of the ion exchange layer and T is the IOX time required to reach that DOL.
[0140] The glass-based article may include an amorphous substrate, a crystalline substrate, or a combination thereof (e.g., a glass-ceramic substrate). In one or more embodiments, the glass-based article substrate (before undergoing chemical strengthening as described herein) may include a glass composition including, in mole percent (mol%), SiO2 in the range of about 40 to about 80, Al2O3 in the range of about 10 to about 30, B2O3 in the range of about 0 to about 10, RO in the range of about 0 to about 20, and RO in the range of about 0 to about 15. In some cases, the composition may include either or both of ZrO2 in the range of about 0 mol% to about 5 mol% and P2O5 in the range of about 0 mol% to about 15 mol%. TiO2 may be present at about 0 mol% to about 2 mol%.
[0141] In some embodiments, the glass composition can include an amount of SiO2, in mole percent, in the range of about 45 to about 80, about 45 to about 75, about 45 to about 70, about 45 to about 65, about 45 to about 60, about 45 to about 65, about 45 to about 65, about 50 to about 70, about 55 to about 70, about 60 to about 70, about 70 to about 75, about 70 to about 72, or about 50 to about 65.
[0142] In some embodiments, the glass composition can include Al2O3 in an amount, in mole percent, in the range of about 5 to about 28, about 5 to about 26, about 5 to about 25, about 5 to about 24, about 5 to about 22, about 5 to about 20, about 6 to about 30, about 8 to about 30, about 10 to about 30, about 12 to about 30, about 14 to about 30, about 16 to about 30, about 18 to about 30, about 18 to about 28, or about 12 to about 15.
[0143] In one or more embodiments, the glass composition may include an amount of B2O3 in mole percent ranging from about 0 to about 8, about 0 to about 6, about 0 to about 4, about 0.1 to about 8, about 0.1 to about 6, about 0.1 to about 4, about 1 to about 10, about 2 to about 10, about 4 to about 10, about 2 to about 8, about 0.1 to about 5, or about 1 to about 3. In some cases, the glass composition may be substantially free of B2O3. As used herein, the phrase "substantially free" with respect to a component of a glass composition means that the component is not actively or intentionally added to the glass composition during initial batching or subsequent ion exchange, but may be present as an impurity. For example, a glass may be described as substantially free of a component if the component is present in an amount less than about 0.1001 mole percent.
[0144] In some embodiments, the glass composition can include one or more alkaline earth metal oxides, such as MgO, CaO, and ZnO. In some embodiments, the total amount of the one or more alkaline earth metal oxides can be a non-zero amount up to about 15 mol%. In one or more specific embodiments, the total amount of any alkaline earth metal oxide can be a non-zero amount up to about 14 mol%, up to about 12 mol%, up to about 10 mol%, up to about 8 mol%, up to about 6 mol%, up to about 4 mol%, up to about 2 mol%, or up to about 1.5 mol%. In some embodiments, the total amount of the one or more alkaline earth metal oxides can be in the range of about 0.1 to 10, about 0.1 to 8, about 0.1 to 6, about 0.1 to 5, about 1 to 10, about 2 to 10, or about 2.5 to 8, in mol%. The amount of MgO can be in the range of about 0 mol% to about 5 mol% (e.g., about 2 mol% to about 4 mol%, about 0.01 to about 2, or about 0.001 to about 1). The amount of ZnO can be in the range of about 0 to about 2 mol % (e.g., about 1 to about 2). The amount of CaO can be about 0 mol % to about 2 mol %. In one or more embodiments, the glass composition can include MgO and can be substantially free of CaO and ZnO. In one variation, the glass composition can include either one of CaO or ZnO and can be substantially free of another of MgO, CaO, and ZnO. In one or more specific embodiments, the glass composition can include only two of the alkaline earth metal oxides MgO, CaO, and ZnO and can be substantially free of a third alkaline earth metal oxide.
[0145] The total amount of alkali metal oxides, R2O, in the glass composition can be in the range, in mole percent, of about 5 to about 20, about 5 to about 18, about 5 to about 16, about 5 to about 15, about 5 to about 14, about 5 to about 12, about 5 to about 10, about 5 to about 8, about 5 to about 20, about 6 to about 20, about 7 to about 20, about 8 to about 20, about 9 to about 20, about 10 to about 20, about 11 to about 20, about 12 to about 18, or about 14 to about 18.
[0146] In one or more embodiments, the glass composition includes Na2O in an amount ranging from about 0 mol% to about 18 mol%, from about 0 mol% to about 16 mol%, or from about 0 mol% to about 14 mol%, from about 0 mol% to about 12 mol%, from about 2 mol% to about 18 mol%, from about 4 mol% to about 18 mol%, from about 6 mol% to about 18 mol%, from about 8 mol% to about 18 mol%, from about 8 mol% to about 14 mol%, from about 8 mol% to about 12 mol%, or from about 10 mol% to about 12 mol%. In some embodiments, the composition includes Na2O in an amount ranging from about 4 mol% or more.
[0147] In some embodiments, the amounts of Li2O and Na2O are controlled to specific amounts or ratios to balance formability and ion exchangeability. For example, increasing the amount of Li2O may decrease the liquidus viscosity, thus preventing the use of some forming methods, but such glass compositions are ion-exchanged at deeper DOC levels as described herein. The amount of Na2O may change the liquidus viscosity, but may hinder ion exchange at deeper DOC levels.
[0148] In one or more embodiments, the glass composition may include KO in an amount less than about 5 mol%, less than about 4 mol%, less than about 3 mol%, less than about 2 mol%, or less than about 1 mol%. In one or more alternative embodiments, the glass composition may be substantially free of KO as defined herein.
[0149] In one or more embodiments, the glass composition can include Li2O in an amount between about 0 mol% and about 18 mol%, between about 0 mol% and about 15 mol%, or between about 0 mol% and about 10 mol%, between about 0 mol% and about 8 mol%, between about 0 mol% and about 6 mol%, between about 0 mol% and about 4 mol%, or between about 0 mol% and about 2 mol%. In some embodiments, the glass composition can include Li2O in an amount between about 2 mol% and about 10 mol%, between about 4 mol% and about 10 mol%, between about 6 mol% and about 10 mol%, or between about 5 mol% and about 8 mol%. In one or more alternative embodiments, the glass composition can be substantially free of Li2O as defined herein.
[0150] In one or more embodiments, the glass composition may include Fe2O3. In such embodiments, Fe2O3 may be present in an amount less than about 1 mol%, less than about 0.9 mol%, less than about 0.8 mol%, less than about 0.7 mol%, less than about 0.6 mol%, less than about 0.5 mol%, less than about 0.4 mol%, less than about 0.3 mol%, less than about 0.2 mol%, less than about 0.1 mol%, and all ranges and subranges therebetween. In one or more further embodiments, the glass composition may be substantially free of Fe2O3 as defined herein.
[0151] In one or more embodiments, the glass composition may include ZrO2. In such embodiments, ZrO2 may be present in an amount less than about 1 mol%, less than about 0.9 mol%, less than about 0.8 mol%, less than about 0.7 mol%, less than about 0.6 mol%, less than about 0.5 mol%, less than about 0.4 mol%, less than about 0.3 mol%, less than about 0.2 mol%, less than about 0.1 mol%, and all ranges and subranges therebetween. In one or more alternative embodiments, the glass composition may be substantially free of ZrO2 as defined herein.
[0152] In one or more embodiments, the glass composition can include P2O5 in the range of about 0 mol% to about 10 mol%, about 0 mol% to about 8 mol%, about 0 mol% to about 6 mol%, about 0 mol% to about 4 mol%, about 0.1 mol% to about 10 mol%, about 0.1 mol% to about 8 mol%, about 2 mol% to about 8 mol%, about 2 mol% to about 6 mol%, or about 2 mol% to about 4 mol%. In some cases, the glass composition can be substantially free of P2O5.
[0153] In one or more embodiments, the glass composition may include TiO2. In such embodiments, TiO2 may be present in an amount less than about 6 mol%, less than about 4 mol%, less than about 2 mol%, or less than about 1 mol%. In one or more other embodiments, the glass composition may be substantially free of TiO2 as defined herein. In some embodiments, TiO2 is present in an amount ranging from about 0.1 mol% to about 6 mol%, or from about 0.1 mol% to about 4 mol%.
[0154] In some embodiments, the glass composition can include various compositional relationships, such as a ratio of the amount of Li2O (in mole %) to the total amount of RO (in mole %) ranging from about 0 to about 1, from about 0 to about 0.5, from about 0 to about 0.4, from about 0.1 to about 0.5, or from about 0.2 to about 0.4.
[0155] In some embodiments, the glass composition can include a difference between the total amount of R2O (in mol%) and the amount of Al2O3 (in mol%) (R2O-Al2O3) in a range of about 0 to about 5 (e.g., about 0 to about 4, about 0 to about 3, about 0.1 to about 4, about 0.1 to about 3, about 0.1 to about 2, or about 1 to about 2).
[0156] In some embodiments, the glass composition has an R in the range of about 0 to about 5 (e.g., about 0 to about 4, about 0 to about 3, about 0.1 to about 4, about 0.1 to about 3, about 1 to about 3, or about 2 to about 3). x The difference between the total amount of O (in mole %) and the amount of Al2O3 (in mole %) (R x O-Al2O3).
[0157] In some embodiments, the glass composition can include a ratio of the total amount of R2O (in mole %) to the amount of Al2O3 (in mole %) (R2O / Al2O3) in the range of about 0 to about 5 (e.g., about 0 to about 4, about 0 to about 3, about 1 to about 4, about 1 to about 3, or about 1 to about 2).
[0158] In one or more embodiments, the glass composition includes a combined amount of Al2O3 and Na2O greater than about 15 mol% (e.g., greater than 18 mol%, greater than about 20 mol%, or greater than about 23 mol%). The combined amount of Al2O3 and Na2O can be up to about 30 mol%, about 32 mol%, or about 35 mol%, inclusive.
[0159] The glass composition of one or more embodiments may exhibit a ratio of the amount of MgO (in mole %) to the total amount of RO (in mole %) ranging from about 0 to about 2.
[0160] In some embodiments, the glass composition may be substantially free of nucleating agents. Examples of typical nucleating agents are TiO2, ZrO2, etc. Nucleating agents can be described in terms of their function: they are components in the glass that can initiate the formation of crystallites in the glass.
[0161] In some embodiments, the composition used in the glass substrate can be formulated with 0-2 mol % of at least one fining agent selected from the group including Na2SO4, NaCl, NaF, NaBr, K2SO4, KCl, KF, KBr, and SnO2. The glass composition according to one or more embodiments can further include SnO2 in the range of about 0 to about 2, about 0 to about 1, about 0.1 to about 2, about 0.1 to about 1, or about 1 to about 2. The glass compositions disclosed herein can be substantially free of As2O3 and / or Sb2O3.
[0162] In one or more embodiments, the composition can include, among others, 62 mol% to 75 mol% SiO2; 10.5 mol% to about 17 mol% Al2O3; 5 mol% to about 13 mol% Li2O; 0 mol% to about 4 mol% ZnO; 0 mol% to about 8 mol% MgO; 2 mol% to about 5 mol% TiO2; 0 mol% to about 4 mol% B2O3; 0 mol% to about 5 mol% Na2O; 0 mol% to about 4 mol% K2O; 0 mol% to about 2 mol% ZrO2; 0 mol% to about 7 mol% PO5; 0 mol% to about 0.3 mol% Fe2O3; 0 mol% to about 2 mol% MnOx; and 0.05 mol% to about 0.2 mol% SnO2.
[0163] In one or more embodiments, the composition can include 67 mol% to about 74 mol% SiO2; 11 mol% to about 15 mol% Al2O3; 5.5 mol% to about 9 mol% Li2O; 0.5 mol% to about 2 mol% ZnO; 2 mol% to about 4.5 mol% MgO; 3 mol% to about 4.5 mol% TiO2; 0 mol% to about 2.2 mol% B2O3; 0 mol% to about 1 mol% Na2O; 0 mol% to about 1 mol% K2O; 0 mol% to about 1 mol% ZrO2; 0 mol% to about 4 mol% PO5; 0 mol% to about 0.1 mol% Fe2O3; 0 mol% to about 1.5 mol% MnOx; and 0.08 mol% to about 0.16 mol% SnO2.
[0164] In one or more embodiments, the composition can include 70 mol% to 75 mol% SiO2; 10 mol% to about 15 mol% Al2O3; 5 mol% to about 13 mol% Li2O; 0 mol% to about 4 mol% ZnO; 0.1 mol% to about 8 mol% MgO; 0 mol% to about 5 mol% TiO2; 0.1 mol% to about 4 mol% B2O3; 0.1 mol% to about 5 mol% Na2O; 0 mol% to about 4 mol% K2O; 0 mol% to about 2 mol% ZrO2; 0 mol% to about 7 mol% PO5; 0 mol% to about 0.3 mol% Fe2O3; 0 mol% to about 2 mol% MnOx; and 0.05 mol% to about 0.2 mol% SnO2.
[0165] In one or more embodiments, the composition can include 52 mol% to about 65 mol% SiO2; 14 mol% to about 18 mol% Al2O3; 5.5 mol% to about 7 mol% Li2O; 1 mol% to about 2 mol% ZnO; 0.01 mol% to about 2 mol% MgO; 4 mol% to about 12 mol% Na2O; 0.1 mol% to about 4 mol% P2O5; and 0.01 mol% to about 0.16 mol% SnO2. In some embodiments, the composition can be substantially free of any one or more of B2O3, TiO2, K2O, and ZrO2.
[0166] In one or more embodiments, the composition can include 0.5 mol% or more of P2O5, Na2O, and optionally Li2O, and Li2O (mol%) / Na2O (mol%) < 1. Further, these compositions may be substantially free of B2O3 and K2O. In some embodiments, the composition can include ZnO, MgO, and SnO2.
[0167] In some embodiments, the composition can include from about 58 mol% to about 65 mol% SiO2; from about 11 mol% to about 19 mol% Al2O3; from about 0.5 mol% to about 3 mol% P2O5; from about 6 mol% to about 18 mol% Na2O; from 0 mol% to about 6 mol% MgO; and from 0 mol% to about 6 mol% ZnO. In one embodiment, the composition can include from about 63 mol% to about 65 mol% SiO2; from 11 mol% to about 17 mol% Al2O3; from about 1 mol% to about 3 mol% P2O5; from about 9 mol% to about 20 mol% Na2O; from 0 mol% to about 6 mol% MgO; and from 0 mol% to about 6 mol% ZnO.
[0168] In some embodiments, the composition can include a compositional relationship of R2O (mol%) / Al2O3 (mol%) < 2, where R2O = Li2O + Na2O. In some embodiments, 65 mol% < SiO2 (mol%) + P2O5 (mol%) < 67 mol%. In one embodiment, R2O (mol%) + R’O (mol%) - Al2O3 (mol%) + P2O5 (mol%) > -3 mol%, where R2O = Li2O + Na2O and R’O is the total amount of divalent metal oxides present in the composition.
[0169] Another representative composition of the glassy article before chemical strengthening as described herein is shown in Table 1A. Table 1B lists selected physical properties measured for the examples listed in Table 1A. The physical properties listed in Table 1B are density; low - and high - temperature CTE; strain point, annealing point, and softening point; 10 11Poise temperature, 35kP temperature, 200kP temperature, liquidus temperature, and zircon fracture temperature; zircon fracture and liquidus viscosity; Poisson's ratio; Young's modulus; refractive index, and stress optical coefficient. In some embodiments, the glass-based articles and glass substrates described herein have a high temperature CTE of 30 ppm / ° C. or less and / or a Young's modulus of 70 GPa or more, and in some embodiments, a Young's modulus of up to 80 GPa.
[0170] [Table 1A-1]
[0171] [Table 1A-2]
[0172] [Table 1A-3]
[0173] [Table 1A-4]
[0174] [Table 1A-5]
[0175] [Table 1B-1]
[0176] [Table 1B-2]
[0177] [Table 1B-3]
[0178] [Table 1B-4]
[0179] [Table 1B-5]
[0180] [Table 1B-6]
[0181] [Table 1B-7]
[0182] [Table 1B-8]
[0183] [Table 1B-9]
[0184] When the glass-based article comprises a glass-ceramic, the crystalline phase may include β-spodumene, rutile, gahnite, or other known crystalline phases, and combinations thereof.
[0185] The glass-based article may be substantially flat, although other embodiments may use curved or otherwise molded or shaped substrates. In some cases, the glass-based article may have a 3D or 2.5D shape. The glass-based article may be substantially optically clear and transmissive, and may be free of light scattering. The glass-based article may have a refractive index in the range of about 1.45 to about 1.55. As used herein, the refractive index values are for a wavelength of 550 nm.
[0186] Additionally or alternatively, the thickness of the glass-based article may be constant along one or more dimensions, or may vary along one or more of its dimensions for aesthetic and / or functional reasons. For example, the edges of the glass-based article may be thicker than the more central regions of the glass-based article. The length, width, and thickness dimensions of the glass-based article may also be altered depending on the application or use of the article.
[0187] Glass-based articles can be characterized by the method by which they are formed. For example, glass-based articles can be characterized as float formable (i.e., formed by a float process), downdrawable, and especially fusion formable or slot drawable (i.e., formed by a downdraw process such as a fusion draw process or a slot draw process). In certain embodiments, the glass-based article is fusion formable.
[0188] Float formable glass-based articles can be characterized by a smooth surface and uniform thickness formed by floating molten glass on a bed of molten metal, typically tin. In one exemplary method, molten glass dispensed onto the surface of a molten tin bed forms a floating glass ribbon. As the glass ribbon flows along the tin bath, the temperature gradually decreases and the glass ribbon solidifies into a solid glass-based article that can be pulled from the tin onto rollers. After leaving the bath, the glass-based article can be annealed to further cool and reduce internal stresses. If the glass-based article is a glass-ceramic, the glass-based article formed by the float process can be subjected to a ceramization process in which one or more crystalline phases are formed.
[0189] The down-draw process produces glass-based articles with relatively pristine surfaces and uniform thickness. A pristine surface that has had minimal contact will have a higher initial strength, since the average bending strength of the glass-based article is controlled by the amount and size of surface scratches. If this high-strength glass-based article is then further strengthened (e.g., chemically), the resulting strength may be higher than that of a glass-based article with a lapped and polished surface. A down-drawn glass-based article can be drawn to a thickness of less than about 2 mm. Furthermore, a down-drawn glass-based article has a very flat and smooth surface that can be used for its end use without costly grinding and polishing. If the glass-based article is a glass-ceramic, the glass-based article formed by the down-draw process can be subjected to a ceramization process in which one or more crystalline phases are formed.
[0190] The fusion draw process employs, for example, a drawing tank having a channel for receiving molten glass raw material. The channel has a weir open at the top along the length of the channel on both sides of the channel. When the channel is filled with molten material, the molten glass spills over the weir. Due to gravity, the molten glass flows down the outer surfaces of the drawing tank as two flowing glass films. These outer surfaces of the drawing tank extend downward and inward to meet at the lower end of the drawing tank. At this end, the two flowing glass films meet and fuse to form one flowing glass-based article. The fusion draw process has the advantage that neither outer surface of the resulting glass-based article comes into contact with any part of the apparatus because the two glass films flowing over the channel fuse together. Thus, the surface properties of the fusion drawn glass-based article are not affected by such contact. If the glass-based article is a glass-ceramic, the glass-based article formed by the fusion process can undergo a ceramization process in which one or more crystalline phases are formed.
[0191] The slot draw process differs from the fusion draw process in that molten raw glass is fed into a draw tank. The bottom of the draw tank has an open slot with a nozzle that extends along the length of the slot. The molten glass flows through the slot / nozzle and is drawn downward as a continuous glass-based article into an annealing zone.
[0192] Glass-based articles can be acid polished or otherwise treated to eliminate or reduce the effects of surface scratches.
[0193] Another aspect of the present disclosure relates to a method of forming a fracture-resistant glass-based article. The method includes providing a glass-based substrate having a first surface and a second surface that define a thickness of about 1 millimeter or less, and generating a stress profile in the glass-based substrate as described herein to obtain a fracture-resistant glass-based article. In one or more embodiments, generating the stress profile includes performing an ion exchange of a plurality of alkali ions in the glass-based substrate to form a non-zero alkali metal oxide concentration that varies along a substantial portion of the thickness (as described herein) or along the entire thickness. In one example, generating the stress profile includes immersing the glass-based substrate in a molten salt bath that includes nitrates of Na+, K+, Rb+, Cs+, or combinations thereof and has a temperature of about 350° C. or greater (e.g., about 350° C. to about 500° C.). In one example, the molten bath can include NaNO3, KNO3, or combinations thereof and can have a temperature of about 485° C. or less. In another example, the bath can include a mixture of NaNO3 and KNO3 and can have a temperature of about 460° C. The glass-based substrate can be immersed in the bath for about 2 hours or more, up to about 48 hours (e.g., about 2 hours to about 10 hours, about 2 hours to about 8 hours, about 2 hours to about 6 hours, about 3 hours to about 10 hours, or about 3.5 hours to about 10 hours).
[0194] In some embodiments, the method can include chemically strengthening or ion exchanging the glass-based substrate in one bath or in two or more steps using successive immersion steps in two or more baths. For example, two or more baths can be used in succession. The composition of one or more baths can include one metal (e.g., Ag+, Na+, K+, Rb+, or Cs+) or a combination of metals in the same bath. When two or more baths are utilized, the baths can have the same or different compositions and / or temperatures from one another. The immersion time in each such bath can be the same or can be varied to obtain a desired stress profile.
[0195] In one or more embodiments of the method, a second or subsequent bath can be utilized to obtain a larger surface CS. In some cases, the method includes immersing the glass-based substrate in a second or subsequent bath to obtain a larger surface CS without significantly affecting the chemical depth and / or DOC of the layer. In such embodiments, the second or subsequent bath can include one metal (e.g., KNO3 or NaNO3) or a mixture of metals (KNO3 and NaNO3). The temperature of the second or subsequent bath can be adjusted to obtain a larger surface CS. In some embodiments, the immersion time of the glass-based substrate in the second or subsequent bath can also be adjusted to obtain a larger surface CS without affecting the chemical depth and / or DOC of the layer. For example, the immersion time in the second or subsequent bath can be less than 10 hours (e.g., about 8 hours or less, about 5 hours or less, about 4 hours or less, about 2 hours or less, about 1 hour or less, about 30 minutes or less, about 15 minutes or less, or about 10 minutes or less).
[0196] In one or more further embodiments, the method can include one or more heat treatment steps that can be used in combination with the ion exchange processes described herein. The heat treatment includes heat treating the glass-based article to obtain a desired stress profile. In some embodiments, the heat treatment includes slow cooling, tempering, or heating the glass-based substrate to a temperature in the range of about 300° C. to about 600° C. The heat treatment can last from 1 minute up to about 18 hours. In some embodiments, the heat treatment can be used after one or more ion exchange processes or multiple ion exchange processes.
[0197] Another aspect of the present disclosure is a method for manufacturing a semiconductor device comprising: a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm; The stress profile extending through the thickness (t) A glass-based article comprising: at least one point of the stress profile within a first thickness range of about 0·t up to 0.020·t and greater than 0.98·t includes a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 200 MPa / micrometer to about 25 MPa / micrometer; all points of the stress profile within a second thickness range of about 0.035·t to less than 0.965·t include a tangent having a slope of about −15 MPa / micrometer to about 15 MPa / micrometer; The stress profile includes a surface CS of about 200 MPa to about 1100 MPa; The stress profile relates to a glass-based article comprising a DOC in the range of about 0.1·t to 0.25·t. In some embodiments, all points of the stress profile within a first thickness range of about 0·t up to 0.020·t and greater than 0.98·t include a tangent with a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 200 MPa / micrometer to about 25 MPa / micrometer. In some embodiments, the referred slope for the second thickness range may be in the range of about 0.1·t to 0.9·t, or 0.15·t to 0.85·t, or 0.2·t to 0.8·t, or 0.22·t to 0.78·t, or 0.24·t to 0.76·t, or 0.26·t to 0.74·t, or 0.28·t to 0.72·t, or 0.3·t to 0.7·t, or 0.35·t to 0.65·t, or 0.4·t to 0.6·t, or 0.45·t to 0.55·t.
[0198] One or more embodiments of the glass-based articles described herein include a particular stress profile that can impart improved scratch performance to the glass surface. Moreover, drop performance (e.g., on both 180-grit and 30-grit sandpaper simultaneously) is not degraded and maintains a reasonable level of performance in field use. Such experimental rough surfaces introduce a series of scratches into the glass that are significant and relevant for field performance. For example, these stress profiles show improved scratch resistance, and good fracture resistance in drop tests is the focus of this disclosure. These stress profiles are also not fragile.
[0199] According to one or more embodiments, stress profiles are disclosed for the diffusion of multiple ions that result in surprising improvements in scratch performance. Some stress profiles can be obtained with one ion exchange step, others with two or more ion exchange steps. In one or more embodiments, the stress profile shows two regions, a spike region with a larger slope followed by a deep tail with a substantially smaller slope, resulting in a very large compression depth, defined as the point where the stress changes from compressive to tensile in the glass.
[0200] In embodiments involving thin glass (i.e., thicknesses ranging from 0.05 mm to 2 mm), the diffusion process is long enough to allow a significant portion of the Na ions exchanged into the glass from the ion exchange bath to reach the center of the glass, such that the deep profile in the two halves of the thickness is connected to a middle portion that does not have a central region of substantially constant Na concentration equal to the original Na concentration in the non-ion exchanged substrate. In one or more embodiments, the time of ion exchange is greater than 1 hour, greater than 1.5 hours, greater than 2 hours, greater than 2.5 hours, greater than 3 hours, greater than 3.5 hours, greater than 4 hours, greater than 4.5 hours, greater than 5 hours, greater than 5.5 hours, greater than 6 hours, greater than 6.5 hours, greater than 7 hours, greater than 7.5 hours, and greater than 8 hours.
[0201] In one or more embodiments, the stress profile results in a non-fragile article.As used herein, "non-fragile" means that when glass is broken, it breaks into several relatively large pieces.In contrast, fragile glass breaks into very small pieces, and glass particles may be released over long distances due to the high elastic energy stored in the glass article.
[0202] The glass-based article of one or more embodiments includes a first surface and a second surface opposite the first surface, the first surface defining a thickness t. In one or more embodiments, the thickness t can be about 2 millimeters or less (e.g., in the range of about 0.01 millimeters to about 2 millimeters, about 0.1 millimeters to about 2 millimeters, about 0.2 millimeters to about 2 millimeters, about 0.3 millimeters to about 2 millimeters, about 0.4 millimeters to about 2 millimeters, about 0.01 millimeters to about 1.75 millimeters, about 0.01 millimeters to about 1.5 millimeters, about 0.01 millimeters to about 1 millimeter, about 0.01 millimeters to about 0.9 millimeters, about 0.01 millimeters to about 0.8 millimeters, about 0.01 millimeters to about 0.7 millimeters, about 0.01 millimeters to about 0.6 millimeters, about 0.01 millimeters to about 0.5 millimeters, about 0.1 millimeters to about 0.5 millimeters, or about 0.3 millimeters to about 0.5 millimeters).
[0203] The stress profile of one or more embodiments is characterized by the presence of two distinct regions with tangents having slopes within a certain range, a region with a relatively steep slope and a region with a shallow slope. In general, the stress profile can be achieved in two different ways. The first method is characterized by one ion exchange diffusion in which two or more types of ions are diffused simultaneously. The second method is characterized by two or more ion exchange diffusions in which two or more types of ions are diffused simultaneously. Each method has certain advantages. For example, one ion exchange diffusion step may be simpler and easier to implement and / or control. However, multiple ion exchange diffusion steps may provide more freedom to tailor the stress profile. In one or more embodiments, the ion exchange time is greater than 1 hour, greater than 1.5 hours, greater than 2 hours, greater than 2.5 hours, greater than 3 hours, greater than 3.5 hours, greater than 4 hours, greater than 4.5 hours, greater than 5 hours, greater than 5.5 hours, greater than 6 hours, greater than 6.5 hours, greater than 7 hours, greater than 7.5 hours, and greater than 8 hours.
[0204] In the stress profile described herein, which includes two regions in one step, it is believed that the larger K ions diffuse slower. In contrast, the smaller Na ions diffuse faster and penetrate deeper. It is also believed that larger K ions result in larger stresses due to the larger specific volume change and therefore the shallower spike in the CS.
[0205] In general, stress profiles with large DOC and high CS spikes help to reduce frontal damage-induced fractures and also help to keep overstress fractures at an acceptable rate. These profiles allow for improved results in Li-containing glasses, which provide the ability to rapidly achieve large compression depths through rapid ion-exchange interdiffusion of Na and Li ions. At the same time, they also allow for high compression (spike) surface layers through potassium (K) diffusion to shallow depths of around 5-15 micrometers. With one ion exchange, on the one hand, medium to high spike depths of layer (DOL) can be achieved. sp ) at the surface, and the knee stress CS at the bottom of the highly compressive surface layer, which is the depth at which the stress gradient changes significantly. k There is a trade-off between
[0206] One problem with Li-containing glasses that have significant amounts of both Li and Na in the unstrengthened matrix is the relatively high Cs k One drawback of this approach is that single ion exchange (SIOX, i.e., ion exchange performed in one bath or step, as opposed to "DIOX", which stands for double ion exchange, i.e., ion exchange performed on the same substrate or glass-based article in two baths or steps) profiles tend to have a limited depth of compression (DOC) due to the large positive curvature in the deeper parts of the profile resulting from the strong nonlinear diffusion.
[0207] With this disclosure, CS and CS k There is no longer a trade-off between high CS and relatively high CS kwhile still achieving a relatively high DOL sp Furthermore, the present invention substantially increases the DOC by substantially reducing the positive curvature in the deeper parts of the profile and possibly even introducing negative curvature in parts of the compression region.
[0208] In some embodiments, both steps are performed using NaCl, such as NaNO3 and KNO3. + ions and K + A two-step process of ion exchange is used, with a mixture of salts containing ions. The first step salt mixture can have a higher Na content than the second step salt mixture. For example, the first step mixture can have 38-90 wt% NaNO3 when the salt mixture is NaNO3+KNO3. The first step salt mixture can have an intermediate surface concentration (e.g., <5 mol%) with a K2O spike near the surface, and no substantial CS despite the presence of a K spike. k In the first step, a substantial central tension CT can also be formed, typically exceeding 60 MPa.
[0209] The second step can be carried out in a salt mixture that is substantially less Na-containing salt (e.g., 3-15 wt. % NaNO3), and further, the second step can be substantially shorter (in some embodiments up to 3 times shorter) than the first step, or at a substantially lower temperature.
[0210] This process takes advantage of the nonlinear diffusion of K when the base glass has a very small amount of K2O, less than about 8% of the total alkali oxide molar content in the glass. For example, the spike in the second step has a substantially larger K2O concentration than the first step. + The effective diffusion coefficient of ions is KThe small amount of Na in the salt mixture of the second step serves the purpose of preventing outward diffusion of Na in the spike, and therefore allows the CS to be maintained at a high DOL with a short second step without sacrificing too much ion exchange temperature or time. k does not vary much, it serves to obtain a relatively stable process.
[0211] The resulting profile has a high CS similar to that obtained using the second mixture alone. Moreover, this is in line with the typical CS of the second step salt alone. k Although it is substantially higher (by more than 10 MPa) than the CS K Substantially lower CS (by more than 10 MPa) than k After a short second step, a relatively high CT is maintained or possibly slightly increased. This CT is substantially higher than the maximum CT that can be obtained by using only the second step salt composition. Finally, the stress profile is often about .2·t (20% of the substrate thickness) and can have a DOC greater than the maximum depth possible with either the first or second salt mixture when used alone.
[0212] During use, the same cover glass part experiences different use stresses (meaning wear effects) on the front (outer) side, the back (inner) side and on the edges. The most common causes of fracture (breakage) include fracture due to the introduction of deep flaws (>10 μm) whose tip depth may even exceed the depth of compression (DOC) that can be obtained by chemical strengthening, and fracture due to overstress (OS) of relatively shallow flaws (1-10 μm) subjected to high local tensions of several hundred MPa. Very often, fracture can be initiated when deep flaws with tip depths somewhat smaller than the DOC are exposed to moderate tensions due to small bending of the cover glass part during use. Among the beneficial parameters of chemical strengthening are therefore large DOC and values of compressive stresses at relatively large depths in the deep compression layer. Such deep flaws can be introduced into the glass during contact with rough surfaces or sharp objects.
[0213] One advantage of the two-step process, when performed in a suitable manner as disclosed herein, is that the deep portion and spike of the profile are obtained substantially independently: changes in the deep portion of the profile during the short, relatively low temperature "spike" step are almost negligible (typically less than 1% changes in DOL and deep stresses and small changes in DOC).
[0214] Li-containing glasses offer certain useful properties for obtaining spiked profiles with very large DOCs, but also present some major problems. One advantage is that very large DOCs can be obtained using relatively short ion exchanges at temperatures much lower than the softening point of the glass. The higher diffusivities of the smaller Na and Li compared to K and Na, respectively, allow Na to exchange with Li deep in the glass much faster than K can exchange to a similar depth as Na, so a large DOC can be achieved quickly. This advantage also presents a problem, since the formation of high CS surface spikes in Li-containing glasses requires K+ ions to diffuse inward to the desired depth, typically about 10 μm. The very low diffusivity of K in Li-based glasses relative to that of Na means that the surface compression spikes performed in a nominally pure KNO3 bath with a first step of ion exchange in pure NaNO3 or exchange in a NaNO3-LiNO3 mixture followed by a second step results in a high DOL. sp Depths greater than DOL sp This generally means that the level of compaction in the aqueous solution (from the aqueous solution to the DOC) is greatly reduced, because the gradient of Na ions obtained after the first ion exchange step is greatly reduced during the spike formation (second ion exchange) step.
[0215] Furthermore, some Li-containing glasses of commercial interest contain both Li2O and Na2O in significant and comparable amounts in the base glass. In one example, one commercially available glass from Corning Incorporated (Corning, NY) contains about 6 mol% Li2O and 11 mol% Na2O. Similarly, another commercially available glass from Corning Incorporated (Corning, NY) contains about 6 mol% Li2O and about 9 mol% Na2O. When a glass having such a composition with significant amounts of both Li2O and Na2O is ion-exchanged in a bath designed to obtain a glass substantially rich in Na at the expense of Li, the resulting Na concentration profile tends to have a very large positive curvature as a result of substantially nonlinear diffusion. As a result, the deep portion of the stress profile at depths beyond the spike depth also has a large positive curvature when significant, such as above 120 MPa. See, for example, curves 2801 (Comparative Example 7B) and 2802 (Comparative Example 7C) in FIG. 36, discussed in more detail below. Such a profile tends to result in significant levels of compressive stress at smaller and intermediate depths, and relatively low compressive stress at larger depths close to the compressive depth. See FIG. 36, where curves 2801 and 2802 fall below curve 2804 (Example 7A). Furthermore, they are consistent with the spike depth DOL sp and similar CS of compressive stress in the region between DOC. k36, where curve 2801 has about the same CS as curve 2804 at 50 micrometers (1 / 3 of the DOC, about 150 micrometers), but a lower CS than curve 2804 by 100 micrometers (about 2 / 3 of the DOC). Similarly, again in FIG. 36, curve 2802 has a CS already smaller than curve 2804 by 50 micrometers (about 1 / 3 of the DOC), and is still smaller than curve 2802 at 75 micrometers (about 1 / 2 DOC) and 100 micrometers (about 2 / 3 of the DOC). Moreover, such profiles (such as curves 2801 and 2802) tend to have less curvature deep in the compression region and somewhat smaller DOC than profiles with similar spikes and similar knee stresses, such as those obtainable in glasses with large amounts of LiO but little or no NaO in the unreinforced composition.
[0216] In chemically strengthened Li-containing cover glass, one of the benefits of chemical strengthening is realized when the DOC is in a stable regime. The DOC is stabilized at around 20% of the thickness (where DOC is around 0.2t), and profiles with larger positive curvatures usually have somewhat smaller values, while profiles with smaller positive curvatures or even negative curvatures tend to have somewhat larger values of DOC. In this stable DOC regime, during field use, the cover glass may be subject to deep scratches formed by sharp objects such as sand particles or pebbles. The strength-limiting scratches are most often the deepest scratches, and having larger compressive stresses at large depths, such as in the 0.3DOC to DOC range, may be beneficial to reduce the likelihood of fracture as a result of sharp contact events. This becomes especially important for smaller thicknesses, such as 1 mm or less, e.g. 0.8 mm or less or 0.6 mm or less, because the DOC decreases proportionally to the thickness and the tip of the flaw, which needs to be arrested by compressive stress, reaches a larger portion of the DOC.
[0217] The present disclosure is particularly directed to large spike DOL, large spike CS, deep DOC, large CS k We describe a dual ion exchange process that can simultaneously achieve large compressive stresses at large depths, from 0.3DOC to 0.3DOC (in some embodiments, as a result of small positive curvatures in the deep parts of the compressive stress profile).
[0218] Some embodiments provide a desired level of CS for good fracture resistance while simultaneously achieving good spike depth and high CS. k This can include improved scratch resistance as a result of achieving
[0219] In some embodiments, the stress profile obtained by two-step (or more) ion exchange of lithium-containing glasses has substantial advantages over the profiles that can be obtained in the same glasses by either one-step ion exchange in a mixed bath of Na- and K-containing salts, or by conventional two-step ion exchange.
[0220] The stress profile obtained using DIOX with a relatively long step in 100% NaNO3 followed by a shorter second step in a mixture of NaNO3 and KNO3 results in a higher CS compared to the SIOX process using the same salt mixture as the DIOX second step. k and small DOL sp A trade-off between the two is most often obtained. Both the first and second steps of the ion exchange are carried out in a mixture of KNO3 and NaNO3, but unlike DIOX (with step 1 having 65% Na, step 2 having 40% Na), a better DIOX profile is obtained if the second step bath has a molar ratio of Na:K substantially smaller (e.g., 1 / 3 to 1 / 10) than that of the first step bath.
[0221] Stress profiles in Li-containing glasses according to some embodiments are obtained by a two-step ion exchange in which both steps of ion exchange are performed in baths containing both Na- and K-containing salts, and the ratio of Na ions to K ions in the first bath is 2.5 times or more, such as 3 times or more, or 5 times or 8 times or more, but 800 times or less, such as 600 times or less, 500 times or less, or 400 times or less, of the ratio of Na ions to K ions in the second bath, depending on the Na:Li ratio in the glass composition. Furthermore, in some embodiments, the second salt has a ratio of Na to K that is 0.03 or more, such as 0.04 or more, or 0.047 or more, in some cases 0.06 or more or 0.07 or more, and 0.4 or less, or 0.35 or less, or 0.30 or less, or 0.21 or less, 0.16 or less, or 0.13 or less, depending on the glass composition. In general, compositions having substantially more Na than Li in the glass will tolerate a larger ratio of Na:K in the bath, for example 0.21 and 0.16, in the second bath. In some embodiments, the effective diffusion time of the second step is 1 / 20 to 1 / 2, such as 1 / 20 to 1 / 3, or 1 / 20 to 1 / 4, of the diffusion time of the first step.
[0222] Some features of the DIOX process described herein are as follows:
[0223] In some embodiments, the high surface CS is very similar to that obtained using a low Na composition in the second step, and is substantially higher than that typically obtained using a high Na first step bath. See, for example, curve 2801 with the high surface CS obtained by a 70Na / 30K bath in Comparative Example 7B, and Example 7A with the curve 2804 for comparison. The surface CS of the DIOX profile can be 600 MPa or more, such as 650 MPa or more, 700 MPa or more, 750 MPa or more, 800 MPa or more, or 850 MPa or more.
[0224] In some embodiments, DOL sp DOL of the first step spand the DOL obtained by the second step alone is equivalent to sp This is much larger (often 2 times, even larger) than the DOL obtained when only the second step has KNO3 in the salt bath, providing K ions for spike formation by ion exchange. sp In comparison, DOL sp In some embodiments, the DOL obtained using the DIOX process disclosed herein is relatively large. sp is in the range of 5 to 16 micrometers, 0.5 to 1.5% of the thickness when the thickness is 1 to 1.3 mm, 0.6 to 2% of the thickness when the thickness is 0.8 to 1 mm, 0.7 to 2.5% when the thickness is 0.65 to 0.8 mm, 0.9 to 3% when the thickness is 0.5 to 0.65 mm, and 1 to 3% when the thickness is 0.3 to 0.5 mm.
[0225] In some embodiments, a relatively high C.S. k The composition of the bath for the second step is typical of CS k The first step CS is substantially larger than k For example, in Example 7A, the CS k The CS of DIOX is about 160MPa. k is 125 MPa, whereas for a bath with a second step composition of 7 wt.% NaNO3 + 93 wt.% KNO3, a Csk of less than 75 MPa is obtained when a stable DOC is achieved.
[0226] In some embodiments, a high DOC is achieved, higher than that achieved by one-step ion exchange with a first step salt. For example, for a 0.8 mm sample, the DOC of the DIOX of Example 7A is about 160 μm, i.e., 20% of the thickness.
[0227] In some embodiments, about 1.5 DOL spThe positive curvature in the compressive stress profile within the depth range of ∼DOC is minimized or even eliminated. In particular, the curvature within that depth range is preferably centered on the center of the substrate and has the same CS as the DIOX profile of the present invention. k It should be noted that for purposes of this comparison, a sign convention is assumed where compressive stress is positive and tensile stress is negative. It should also be noted that for quality control purposes, a simplified representation of the profile as a power law profile with spikes may be assumed. The deep portion of the spiked parabolic profile is fitted to a parabola with a power law coefficient of 2. In some embodiments, for the shape of the deep region of the profile or CT region, the power coefficient may be in the range of 1 to 3 or 1.7 to 2.6. The DIOX profile of the present invention is characterized by the DOL sp and DOC, over the same depth range, depth = DOL sp 4 shows a curvature that does not exceed that of a parabolic profile having the same stress at
[0228] In some embodiments, a relatively large compression can be achieved within the depth range of DOC / 3 to DOC. In particular, the DIOX profile has similar or greater compression than the first step profile within this depth range. For example, comparing curve 2804 of FIG. 36 with curves 2802 and 2803 within the range of about 50 to 150 micrometers shows a larger CS within this range. This larger CS is consistent with the balance of forces and the approximately 1.5 DOL sp ~ This results from the combined effect of a reduction or elimination of the positive curvature of the profile within the DOC depth range.
[0229] In some embodiments, a relatively high CT can be achieved, typically within the range of the first step CT ±3 MPa, typically 5-15 MPa higher than the CT obtained using only the step 2 salt composition for a comparable total ion exchange time. In Example 7, FIG. 36, the DIOX profile (curve 2804) has a CT of about 70 MPa, which is similar to the CT of the one-step curve 2801 profile (70% Na, 4 hours, 380° C.), while ion exchange in the second step bath (7% Na) for a time equivalent to a total DIOX time of 4 hours 40 minutes results in a CT in the range of 50-55 MPa. The high CT of the DIOX profile indicates a high stress-depth integral in the compression zone, which helps the glass article to resist fracture initiated by flaws introduced in the compression zone.
[0230] In some embodiments, a spheroid may have a similar deep portion and a similar high CSk, but a substantially lower surface CS or a smaller DOL sp For example, comparing the SIOX profile of curve 2802 in FIG. 36 obtained in a bath with 40% NaNO3 and 60% KNO3 with the DIOX profile of curve 2804, which has a similar CS at 125 MPa, the SIOX profile of curve 2802 in FIG. k , similar DOC, and DOL sp , but the surface CS of curve 2802 is approximately 250 MPa lower (550-570 MPa versus 800-820 MPa for the DIOX profile of curve 2804).
[0231] In some embodiments, the DIOX profile and the method of making it provide very good strengthening of the peripheral area of the glass article when the thickness of the glass article gradually decreases toward the edge ("2.5D cover glass"). In the case of conventional ("2D") cover glass, the thickness of the glass article is substantially constant right up to the edge of the glass sheet, or to less than 0.3t at the edge tip if the edge is beveled, where t is the thickness of the sheet. The profiles according to the embodiments described herein provide good strengthening of this type of edge compared to prior art profiles, since the compression depth measured from any point around the edge is similar to the large compression depth inside the sheet. More notably, in the case of 2.5D cover glass, where the thickness of the sheet gradually decreases toward the edge, typically at a distance of 1-3 mm from the edge or 0.3t or more from the edge, but most often starting at a distance of 0.5t or more or 1.0t or more from the edge, there is a primary strengthening in the sense that flaws that start at the periphery of the glass article (e.g., at the formation of edge contacts) are more likely to be prevented or deflected by the compressive stress distribution than usual, compared to prior art profiles. This crack arrest effect is a great advantage because, as electronic devices are accidentally dropped and they experience more edge contact events, such edge reinforcement would be beneficial to greatly improve resistance to breakage during actual use.
[0232] Thus, in one or more embodiments at least one point, and in another embodiment all points, of the stress profile within the first thickness range of about 0·t up to 0.020·t and greater than 0.98·t includes a tangent having a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 200 MPa / micrometer to about 25 MPa / micrometer. The first thickness range can range from about 0·t up to about 0.020·t, 0.025·t, 0.0275·t, 0.030·t, or 0.035·t, and greater than 0.98·t, greater than 0.975·t, greater than 0.9725·t, greater than 0.97·t, or greater than 0.965·t. The slope can range from about -200 MPa / micrometer to about -25 MPa / micrometer or about 200 MPa / micrometer to about 25 MPa / micrometer. In further embodiments, the slope may be in the range of about -200, -190, -180, -170, -160, -150, or -140 MPa / micrometer to about -25, -27, -30, -31, -32, -33, -34, or -35 MPa / micrometer, or in the range of about 25, 27, 30, 31, 32, 33, 34, or 35 to about 140, 150, 160, 170, 180, 190, or 200. Thus, for example, in one or more embodiments at least one point, and in another embodiment all points, of the stress profile within the first thickness range include a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer, or about 30 MPa / micrometer to about 170 MPa / micrometer. In some embodiments, at least one point, and in other embodiments all points, of the stress profile within the first thickness range includes a tangent having a slope of about -140 MPa / micrometer to about -35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer.
[0233] The above slope ranges can be combined with any first thickness range. Thus, for example, in one or more embodiments, at least one point, and in another embodiment, all points, of the stress profile within the first thickness range of about 0·t to a maximum of 0.025·t and greater than 0.975·t include a tangent with a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer. In further embodiments, at least one point, and in another embodiment, all points, of the stress profile within the first thickness range of about 0·t to a maximum of 0.025·t and greater than 0.975·t include a tangent with a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In a further embodiment at least one point, and in another embodiment all points, of the stress profile within the first thickness range of about 0·t up to 0.025·t and greater than 0.975·t includes a tangent having a slope of about −140 MPa / micrometer to about −35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer.
[0234] In some embodiments at least one point, and in other embodiments all points, of the stress profile within the first thickness range of about 0·t up to 0.035·t and greater than 0.965·t include a tangent having a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer. In further embodiments at least one point, and in other embodiments all points, of the stress profile within the first thickness range of about 0·t up to 0.035·t and greater than 0.965·t include a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer. In further embodiments at least one point, and in other embodiments all points, of the stress profile within the first thickness range of about 0·t up to 0.035·t and greater than 0.965·t includes a tangent having a slope of about −140 MPa / micrometer to about −35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer. In some embodiments, as the first thickness range narrows, the slope of the tangent to the points at the first thickness may become steeper.
[0235] In one or more embodiments of this aspect, all points of the stress profile within the second thickness range of about 0.035·t to less than 0.965·t include a tangent having a slope of about −15 MPa / micrometer to about 15 MPa / micrometer. That is, as one progresses along the range of 0.035·t to 0.965·t, the slope begins to become negative, approaches zero, then becomes positive, and approaches a power law function. As used herein, “power law function” refers to a curve in which the stress is exponentially proportional to the depth or thickness. In one or more embodiments, the exponent ranges from about 1.2 to about 3.2. In further embodiments, the exponent ranges from about 1.2 to about 2.8. In some embodiments, the slope referred to in the case of the second thickness range may be in the range of about 0.1·t to 0.9·t, or 0.15·t to 0.85·t, or 0.2·t to 0.8·t, or 0.22·t to 0.78·t, or 0.24·t to 0.76·t, or 0.26·t to 0.74·t, or 0.28·t to 0.72·t, or 0.3·t to 0.7·t, or 0.35·t to 0.65·t, or 0.4·t to 0.6·t, or 0.45·t to 0.55·t.
[0236] The points within the second thickness range can also be described as including a tangent having a slope, in one or more embodiments, the slope of the tangent is in the range of about -15, -10, -5, -4, -3, -2, or -1 MPa / micrometer to about 1, 2, 3, 4, 5, 10, or 15 MPa / micrometer. In some embodiments, the slope referred to in the case of the second thickness range may be in the range of about 0.1·t to 0.9·t, or 0.15·t to 0.85·t, or 0.2·t to 0.8·t, or 0.22·t to 0.78·t, or 0.24·t to 0.76·t, or 0.26·t to 0.74·t, or 0.28·t to 0.72·t, or 0.3·t to 0.7·t, or 0.35·t to 0.65·t, or 0.4·t to 0.6·t, or 0.45·t to 0.55·t.
[0237] The above slope ranges can be combined with any second thickness range. Thus, for example, in one or more embodiments, all points of the stress profile within a second thickness range of about 0.035·t to less than 0.965·t include a tangent with a slope of about -2 MPa / micrometer to about 2 MPa / micrometer. In some embodiments, all points of the stress profile within a second thickness range of about 0.025·t to less than 0.975·t include a tangent with a slope of about -15 MPa / micrometer to about 15 MPa / micrometer. In further embodiments, points of the stress profile within a second thickness range of about 0.025·t to less than 0.975·t include a tangent with a slope of about -2 MPa / micrometer to about 2 MPa / micrometer. In one or more embodiments, all points of the stress profile within the second thickness range of about 0.02·t to less than 0.98·t include a tangent having a slope of about −15 MPa / micrometer to about 15 MPa / micrometer or about −2 MPa / micrometer to about 2 MPa / micrometer.
[0238] In one or more embodiments, the glass-based article comprises a surface CS of from about 200 MPa to about 1100 MPa. In further embodiments, the surface CS is greater than about 300, greater than 350, greater than 400, greater than 450, greater than 500, greater than 550, greater than 600, greater than 610, greater than 620, greater than 650, greater than 700, greater than 750, and / or less than about 650, less than 700, less than 750, less than 800, less than 850, less than 900, less than 950, less than 1000, or less than 1100.
[0239] The glass-based article according to one or more embodiments of this aspect comprises a stress profile and a DOC in the range of about 0.1·t to 0.25·t or 0.3·t.
[0240] In one or more embodiments, the glass-based article comprises a composition comprising about 0.5 mol % P2O5 to 10 mol % P2O5.
[0241] The stress profile of the glass-based article of this aspect can be obtained either by one ion-exchange step or using two or more ion-exchange steps. In one or more embodiments, these ion-exchange steps can include or have any of the features previously described in the previous aspects. In one or more embodiments, the first thickness range is obtained by ion-exchange in a potassium-containing salt.
[0242] In one or more embodiments of a one-step ion-exchange process for Li-containing glasses, the primary control parameter is believed to be the bath concentration ratio between Na and K resulting in the relative magnitude of the spike Cs and the stress deep in the profile. A second parameter of lesser influence on that relative magnitude is the ion-exchange time and temperature, both of which can be influenced by the depth of the spike in the profile and the overall stress requirements. Thus, according to one or more embodiments, a method is provided that includes one ion-exchange step that includes varying the concentration ratio between Na and K over time to achieve the stress profile described herein.
[0243] In one or more embodiments of chemical strengthening with two or more ion exchange steps, it is possible to further tailor the profile by using different Na / K ratios and different relative times for these two or more steps. In some embodiments, a range of power coefficients for the tail region of the profile can be achieved by adjusting the KNO3 / NaNO3 ratio and ion exchange time. The experimental profiles provided in this disclosure can have a power function that falls within the range of 1 to 3 or 1.7 to 2.6 due to the shape of the deep region of the profile. Profiles with smaller power coefficients are generally considered to have smaller slopes in the deep region, typically less than 1 MPa / micrometer. Thus, according to one or more embodiments, a method is provided that includes two or more ion exchange steps that include varying the concentration ratio between Na and K over time to achieve the stress profile described herein.
[0244] Another aspect of the present disclosure relates to a glass-based article comprising a central surface comprising about 2 to about 20 mol % Li2O, a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm, and a stress profile extending along the thickness (t), wherein at least one point of the stress profile within the first thickness range of about 0·t up to 0.020·t and greater than 0.98·t comprises a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer, the stress profile comprising a surface C S of about 200 MPa to about 1100 MPa, and the stress profile comprising a DOC in the range of about 0.05·t to 0.25·t. Any of the embodiments described above may be applied to this aspect, particularly with respect to the previous aspect. In another embodiment, all points of the stress profile within a first thickness range from about 0·t up to 0.020·t and greater than 0.98·t include a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer.
[0245] In one or more embodiments, the first thickness range is achieved by ion exchange in a K-containing salt.
[0246] In one or more embodiments, the second thickness range is achieved by ion exchange in a Na- or K-containing salt.
[0247] In one or more embodiments, the stress profile is obtained using one ion exchange step.
[0248] In one or more embodiments, the stress profile is obtained using two or more ion exchange steps.
[0249] In one or more embodiments, the surface CS is in the range of about 690 MPa to 950 MPa.
[0250] In one or more embodiments, all points of the stress profile within the second depth range range from a power law profile having a power exponent, the power exponent being between about 1.2 and 3.4, in some embodiments, the power exponent being between about 1.3 and 2.8.
[0251] In one or more embodiments, the glass-based article comprises a composition including about 0.5 mol % P2O5 to about 10 mol % P2O5.
[0252] In one or more embodiments, the central surface further comprises a composition comprising about 0.5 mol % to about 20 mol % Na2O. In some embodiments, the central surface further comprises a composition comprising about 2 mol % to about 10 mol % Li2O. In some embodiments, the concentration of Na2O within the central surface of the glass article is about 5 mol % to 16 mol %. In some embodiments, the concentration of Na2O within the central surface of the glass article is about 10 mol % to 15 mol %. In some embodiments, the concentration of Li2O within the central surface of the glass article is about 3 mol % to 10 mol %.
[0253] The glass-based articles according to one or more embodiments of the disclosure described herein, especially those containing Li as a major component, have improved levels of scratch resistance without sacrificing drop performance. The glass-based articles according to one or more embodiments of the disclosure described herein have excellent drop performance as shown with both 30-grit and 180-grit abrasive papers. The glass-based articles according to one or more embodiments of the disclosure described herein provide a non-fragile method, with glass breakage being primarily quasi-uniform. The glass-based articles according to one or more embodiments of the disclosure described herein have acceptable levels of glass shape distortion for the temperature and composition used in the ion exchange process. The glass-based articles according to one or more embodiments of the disclosure described herein include stress profiles that can be achieved without complex manufacturing processes.
[0254] In one or more embodiments, it has been determined that the concentration profile in glasses according to the present disclosure differs from a profile based on a complementary error function that can be calculated using a linear diffusion approximation. Thus, glasses according to one or more embodiments described herein do not exhibit a profile based on a complementary error function that can be calculated using a linear diffusion approximation.
[0255] According to one or more embodiments, the interdiffusivity that can be used to describe Na / Li, K / (Na+Li) interdiffusion in glasses according to one or more embodiments depends on the local concentrations of Li, Na, and K. Chemically strengthened Li-containing glasses have been described in the literature. However, such glasses described in the literature ignore the effect of concentration-dependent diffusivity on the curvature of the stress profile, and such glasses exhibit profiles that conform to a linear diffusion approximation (i.e., shallow and deep branches of a complementary error function type of a two-segment profile), distinguishing the glasses of one or more embodiments of the present disclosure from the glasses in the literature. Another difference between the glasses described according to one or more embodiments of the present disclosure and the glasses in the literature is that the diffusion of strengthening ion species (e.g., Na+ or K+ or combinations thereof) in known strengthened substrates does not extend to deeper depths of the substrate, or in some cases, does not extend to the center of the substrate (i.e., within the range of about 0.4t to about 0.6t). Furthermore, the literature does not disclose combinations of glass diffusivity, substrate thickness, and ion exchange conditions that result in the stress profiles described herein. In particular, thicker substrates (e.g., substrates having a thickness of more than 2.5 mm) are described in the literature. In particular, these differences between the glasses according to one or more embodiments of the present disclosure and the glasses described in the literature also result in differences in the overall profile shape, in particular the power law approximation according to one or more embodiments. EXAMPLES
[0256] Various embodiments are further illustrated by the following examples, in which, prior to tempering, the examples are referred to as "substrates." After tempering, the examples are referred to as "articles" or "glass-based articles." Example 1 Examples 1A-1G included glass substrates with nominal compositions of about 63.46 mol% SiO2, 15.71 mol% Al2O3, 6.37 mol% Li2O, 10.69 mol% Na2O, 0.06 mol% MgO, 1.15 mol% ZnO, 2.45 mol% P2O5, and 0.04 mol% SnO2. The glass substrates had a thickness of 0.8 mm. The glass substrates of Examples 1A-1G were ion-exchanged in a molten salt bath containing 100% NaNO3 and having a temperature of about 390°C according to the conditions shown in Table 2. The resulting glass-based articles exhibited maximum CT values plotted as a function of ion-exchange time in FIG. 5.
[0257] [Table 2]
[0258] The stress profile of Example 1E was measured using refractive near-field (RNF) measurements as described in U.S. Pat. No. 8,854,623, entitled "Systems and methods for measuring a profile characteristic of a glass sample," which is incorporated herein by reference in its entirety. FIG. 6 shows the measured stress as a function of the depth extending into the glass-based article from the surface of the glass-based article of Example 1E. The stress at specific depths, including the knee, is shown in Table 3. In FIG. 6, positive numbers are used for compressive stresses and negative numbers indicate tensile stresses. This same convention (compressive stresses are shown as positive values on the y-axis and tensile stresses are shown by negative values on the y-axis) is also used in FIGS. 1-3, 23, and 27. However, in the remaining figures, compressive stresses are shown as negative values on the y-axis and tensile stresses are shown as positive values on the y-axis.
[0259] [Table 3]
[0260] Example 2 Example 2A included a glass substrate having the same composition and thickness of 0.8 mm as Example 1. The glass substrate underwent ion exchange for 3.75 hours in a molten salt bath containing 51% KNO3 and 49% NaNO3 and having a temperature of about 380° C. The resulting glass-based article exhibited the stress profile listed in Table 4.
[0261] [Table 4]
[0262] The glass-based articles according to Example 2A were subjected to AROR testing as described herein. A first set of glass-based articles were abraded using a load or pressure of 5 psi (34.5 kPa), a second set of glass-based articles were abraded using a load or pressure of 25 psi (172 kPa), and a third set of glass-based articles were abraded using a load or pressure of 45 psi (310 kPa). The AROR data is shown in Figure 7. As shown in Figure 7, all of the glass-based articles according to Example 2A exhibited an average failure load of greater than about 20 kgf (about 196 N).
[0263] The glass-based articles according to Example 2A were retrofitted onto the same mobile phone devices. These phone devices were dropped onto 180-grit abrasive paper from increasing heights starting from 20 centimeters. If the glass-based articles survived a drop from a certain height (e.g., 20 cm), the mobile phone was dropped again from higher heights (e.g., 30 cm, 40 cm, 50 cm, etc.) up to a height of 225 cm. The surviving glass-based articles were then dropped (in the same phone device) onto 30-grit abrasive paper. The heights at which the glass-based articles broke on both 180-grit abrasive paper and 30-grit abrasive paper are plotted in FIG. 8. As shown in FIG. 8, all but two of the glass-based articles of Example 2A survived drops onto 180-grit abrasive paper from heights up to about 225 cm (resulting in an average surviving drop height of about 216 cm). The average surviving drop height onto 30-grit abrasive paper was 66 cm, with some surviving drop heights of over 100 cm.
[0264] The glass-based article according to Example 2A exhibited a dielectric constant of about 6.9 to about 7.05 over a frequency range of about 480 mHz to about 3000 mHz. The glass-based article according to Example 2A exhibited a dielectric loss tangent in the range of about 0.012 to about 0.015 over a frequency range of about 480 mHz to about 3000 mHz.
[0265] The refractive index of the glass-based article according to Example 2A is within the range of about 1.158 to about 1.49 over the range of about 380 nm to about 1550 nm, and within the range of about 1.518 to about 1.497 over the wavelength range of about 380 nm to about 800 nm.
[0266] The glass-based article according to Example 2A was subjected to various chemical treatments as shown in Table 5. The chemical durability of the glass-based article was compared with Comparative Examples 2E, 2F, and 2G. Comparative Example 2E was a glass substrate with a nominal composition of 64.3 mol% SiO2, 7.02 mol% B2O3, 14 mol% Al2O3, 14 mol% Na2O, 0.5 mol% K2O, 0.03 mol% Fe2O3, and 0.1 mol% SnO2. Comparative Example 2F was a glass substrate with a nominal composition of 64.75 mol% SiO2, 5 mol% B2O3, 14 mol% Al2O3, 13.75 mol% Na2O, 2.4 mol% MgO, and 0.08 mol% SnO2. Comparative Example 2G included a glass substrate with a nominal composition of 57.5 mol % SiO2, 16.5 mol % Al2O3, 16.71 mol % Na2O, 2.8 mol % MgO, and 0.05 mol % SnO2.
[0267] [Table 5]
[0268] Example 3 Example 3A included a glass substrate having the same composition as Example 1 and a thickness of 0.8 mm. Comparative Example 3B included a glass substrate having the same composition as Comparative Example 2G and a thickness of 0.8 mm. The glass substrate of Example 3A was chemically strengthened in one step using one bath as described in Table 6. The glass substrate of Comparative Example 3B was ion-exchanged in a two-step process as described in Table 6.
[0269] [Table 6]
[0270] The glass-based articles according to Example 3A and Comparative Example 3B were retrofitted onto the same mobile phone device. The phone devices were dropped onto 30-grit abrasive paper from increasing heights starting at 20 centimeters. The heights at which the glass-based articles broke on the 30-grit abrasive paper are plotted in FIG. 9. As shown in FIG. 9, the glass-based article of Example 3A exhibited an average remaining drop height (i.e., 91 cm) that was more than twice as high as that of Comparative Example 3B (i.e., 38 cm).
[0271] The glass-based articles according to Example 3A and Comparative Example 3B were subjected to the AROR test described herein using a load or pressure of 25 psi (172 kPa). As shown in FIG. 10, the glass-based substrate of Example 3A exhibited an average failure load of about 30 kgf (about 294 N), while the glass-based substrate of Comparative Example 3B exhibited an average failure load of about 27 kgf. When the polishing load or pressure was increased to 45 psi (310 kPa), the difference in the average failure load between Example 3A and Comparative Example 3B increased. In particular, under a load or pressure of 45 psi (310 kPa), Example 3A exhibited an average failure load of about 25.9 kgf (about 254 N), while Comparative Example 3B exhibited an average failure load of about 19.6 kgf (about 192 N), as shown in FIG. 11.
[0272] Example 4 Chemical strengthening was performed on glass substrates with a nominal composition of 57.5 mol% SiO2, 16.5 mol% Al2O3, 16.7 mol% Na2O, 2.5 mol% MgO, and 6.5 mol% P2O5 and thicknesses of approximately 0.4 mm, 0.55 mm, or 1 mm. The thicknesses and chemical strengthening conditions are shown in Table 7.
[0273] [Table 7]
[0274] Example 4A was immersed in the molten salt bath shown in Table 7 for 4 hours, 8 hours, 16 hours, 32 hours, 64 hours, and 128 hours (Examples 4A-1 to 4A-6). Example 4B was immersed in the molten salt bath shown in Table 7 for 4 hours, 8 hours, 16 hours, 32 hours, 64 hours, and 128 hours (Examples 4B-1 to 4B-6). Example 4C was immersed in the molten salt bath shown in Table 7 for 1 hour, 2 hours, 4 hours, 8 hours, 16 hours, and 32 hours (Examples 4C-1 to 4C-6). Example 4D was immersed in the molten salt bath shown in Table 7 for 4 hours, 8 hours, 16 hours, 32 hours, 64 hours, and 128 hours (Examples 4D-1 to 4D-6). The stress profiles for Examples 4A-1 through 4A-6, 4B-1 through 4B-6, 6C-1 through 4C-6, and 4D-1 through 4D-6 are shown in Figures 12, 14, 16, and 18, respectively. In Figures 12, 14, 16, and 18, the depth or thickness of the glass article is plotted on the x-axis and stress is plotted on the y-axis. Positive stress values are CT values and negative stress values are CS values.
[0275] The CT and DOC values as a function of immersion time in the molten salt bath for Examples 4A-1 to 4A-6, Examples 4B-1 to 4B-6, Examples 4C-1 to 4C-6, and Examples 4D-1 to 4D-6 are shown in Figures 13, 15, 17, and 19, respectively.
[0276] Example 5 Glass substrates having the nominal composition shown in Table 8 and a thickness of about 0.8 mm were chemically strengthened in a molten salt bath containing a mixture of NaNO3 and NaSO4 and a temperature of 500°C for 15 minutes (Comparative Example 5A) and 16 hours (Example 5B), respectively.
[0277] [Table 8]
[0278] The stress profiles of the glass-based articles of Examples 5A and 5B are shown in Figure 20. As shown in Figure 20, Comparative Example 5A exhibits a known stress profile, while Example 5B exhibits a stress profile according to one or more embodiments of the present disclosure. The stored tensile energy of the glass-based articles of Examples 5A and 5B was calculated from the measured SCALP stress profile data using Equation (3) above. As shown in Figure 21, the calculated stored tensile energy is plotted as a function of measured CT (MPa).
[0279] As shown in FIG. 21, Comparative Example 5A exhibited a much higher stored tensile energy value for a particular CT value than Example 5B (for the same CT value). In this figure, CT is the maximum CT in the sample. Specifically, at a CT of about 55 MPa, Comparative Example 5A exhibited a stored tensile energy value of about 12 J / m 2 tensile energy of about 9 J / m 2 21. When Comparative Example 5A and Example 5B were broken, Example 5B broke into fewer pieces than Comparative Example 5A, and Comparative Example 5A broke into a much larger number of pieces. Thus, without wishing to be bound by theory, it is believed that controlling the stored tensile energy can provide a way to control or predict the fragmentation pattern or number of pieces resulting from fracture. In these examples, the CT was changed by keeping the sample in the ion exchange bath for a longer period of time while using the same bath temperature and composition. In FIG. 21, the 0,0 point is not experimental, but rather the point where one skilled in the art would expect the stored tensile energy to be 0 if that is the case, i.e., if there is a 0 CT.
[0280] Glass substrates having the nominal composition shown in Table 8 and a thickness of about 1 mm were chemically strengthened in a molten salt bath containing NaNO3 and a temperature of 430°C for 4 hours (Comparative Example 5C) and 61.5 hours (Example 5D), respectively. Comparative Example 5C exhibits a known stress profile, while Example 5D exhibits a stress profile according to one or more embodiments of the present disclosure. The stored tensile energy of Examples 5C and 5D was calculated using the same method as used for Examples 5A-5B and is plotted as a function of measured CT (MPa) as shown in Figure 22.
[0281] As shown in Figure 22, Comparative Example 5C exhibited much greater stored tensile energy values than Example 5D (for the same CT value) for a given CT value (again, as in Figure 21, these were maximum CT values, and again these values were varied by using the same ion exchange bath temperature and composition but for a longer time). When Comparative Example 5C and Example 5D broke, Example 5D broke into fewer pieces than Comparative Example 5C, and Comparative Example 5C broke into a much larger number of pieces.
[0282] Example 6 Examples 6A-6D included glass substrates having about 10 mol% Na2O and 6 mol% Li2O in a base glass according to one or more embodiments of the present disclosure. For example, the nominal composition has about 63.46 mol% SiO2, 15.71 mol% Al2O3, 6.37 mol% Li2O, 10.69 mol% Na2O, 0.06 mol% MgO, 1.15 mol% ZnO, 2.45 mol% P2O5, and 0.04 mol% SnO2. These glass substrates have a thickness of 0.8 mm. The glass substrates of Examples 6A-6D were subjected to ion exchange in a molten salt bath including the conditions shown in Table 9, where "SIOX" means one ion exchange and "DIOX" means double ion exchange.
[0283] Various tests of stress profiles have been carried out in glass substrates. The glass substrates have a composition containing Na and Li in the base glass. It is possible to exchange two or more ions, mainly Na and K, with Li at the same time. Typically, a two-step IOX process using different KNO3 / NaNO3 mixtures is carried out in glasses with only one free ion in their composition, such as Na, to achieve a profile with a long tail towards the center of the glass and a spike in its surface.
[0284] [Table 9]
[0285] Table 9 also shows parameters and measurements by point-by-point method and prism bond group measurement (FSM instrument) for stress at the direct outer surface for different ion exchange methods. The parameters shown in Table 9 include the power coefficient of the deep region of the profile, the surface compressive stress (CS), the stress at the knee where the spike connects to the deep tail, and the layer depth of the spike where the knee occurs. As can be seen from Examples 6A-D, the DOL of the spike can be about .01·t to about .035·t (e.g., about .015·t, .02·t, .025·t, .30·t, or .35·t, and any and all subranges therebetween), i.e., about 7.3 micrometers to about 24 micrometers for a sample with a thickness of 800 micrometers. The spike DOL generally corresponds to the potassium DOL. In Li-containing glasses, even one IOX diffusion creates spikes and tails in the stress profile. This is believed to be because glasses containing different amounts of Li, Na, and K are exchanged simultaneously at different diffusion rates. Due to small local deviations between the actual deep stress profile and the power law approximation, and limited precision in point-to-point stress profile measurements, differences of up to 10-15 MPa can occur between the actual stress at the base of the spike and the knee stress of the modeled power law profile with the spike.
[0286] FIG. 23 shows the stress profile measured by point-by-point refractive index measurements in TE and TM polarization. Note that the stress at the surface is shown lower than it actually is in the top 5 micrometers due to the resolution limit of the measurement technique. The actual surface stress values are higher than shown here and are measured separately by the prism coupling technique. A fuller range of properties is shown in Table 9. Note that even one ion exchange (SIOX) diffusion forms a spike and tail in the stress profile when the Li-containing glass is immersed in a bath with both K and Na. Without wishing to be bound by any particular theory, it is believed that this spike and tail is due to the presence of different amounts of Li, Na, and K that are exchanged simultaneously at different diffusion rates.
[0287] An example of a stress profile can be seen in Figure 23. As can be seen from this figure, for Example 6A, the spike region is due to the nonlinear diffusion of potassium, while the tail of the profile is due to the nonlinear diffusion of Na and Li. Even for short diffusion times where Na from the ion exchange bath does not reach the center of the thickness, the tail of the profile in this case is not represented by the complementary error function that is only applicable for substantially linear diffusion.
[0288] In Figure 23 again we can see the measured stress profiles of the various stress profiles tested by point-by-point refractive index measurements in TE and TM polarization. Here the stress at the surface is shown to be lower than it really is due to the limited resolution of the measurements and the large slope of the spike profile. The actual surface stress values may be higher than shown in this figure and are measured separately using the analysis of the mode spectrum obtained using prism coupling (FSM-6000). It should be noted that one ion exchange diffusion will produce spikes and tails in the stress profile because two or more types of ions diffuse simultaneously.
[0289] FIG. 24 shows measured normalized microprobe data for K, Na, and Li diffused using a 51 wt % K / 49 wt % Na formulation at 380° C. for 3.75 hours (6A) in a glass having about 10 mol % Na2O and 6 mol % Li2O in the base glass according to one or more embodiments of the present disclosure. As can be seen, the potassium diffusion is limited to near the glass surface, forming a surface peak in the stress profile. However, the Na profile penetrates very deeply into the center of the glass. As the central Na concentration begins to increase in a substantial way as a result of the two profiles of internally diffused Na merging in the center, the shape of the Na profile can be reasonably approximated by a power law, and is substantially different from the shape before this condition was met. Further compression depth plateaus and changes very little with further diffusion time.
[0290] In Figure 24, after ion exchange diffusion using a 51 wt% K / 49 wt% Na formulation at 380°C for 3.75 hours in a glass originally containing only Na and Li (Example 6A) is shown. It can be seen that potassium diffuses only in the near surface region, forming a surface peak (spike) in the stress profile. However, Na and Li exchange relatively deep into the center of the glass, resulting in a substantially curved stress profile throughout the thickness. We have obtained a regime of ion exchange that can produce the desired curvature profile and can be quantified using a power law model.
[0291] FIG. 25 shows an example of incremental scratch testing of 6A-6D in incremental mode, increasing linearly from 0 Newtons to 4 Newtons from the top to the bottom of the figure, using a diamond tip with a radius of 30 micrometers at an angle of 76.5 degrees at the cone angle.
[0292] Table 10 below shows the percentage of scratches that had cracks when evaluated by optical microscopy in an incremental scratch test as illustrated in FIG.
[0293] [Table 10]
[0294] Tables 11-18 show the rating of scratch severity in several tests by microscopic evaluation.
[0295] [Table 11]
[0296] [Table 12]
[0297] [Table 13]
[0298] [Table 14]
[0299] [Table 15]
[0300] [Table 16]
[0301] [Table 17]
[0302] [Table 18]
[0303] Different stress profiles indicate different levels of scratch susceptibility under certain conditions. An example of an incremental scratch test is shown in FIG. 25 using a diamond tip with a radius of 30 micrometers and a support cone angle of 76.5 degrees. The applied scratch force was increased linearly over the range of 0 Newtons to 4 Newtons. Here, compared to the method of Example 6A in Table 9, it can be seen that the methods of Examples 6B-6D modified to increase the spike CS provide improved scratch performance that can be seen as narrower and less visible scratch defects. Images shown for each method are from five severe tests performed with that method. Observation of the scratch performance reveals some underlying trends when rating severity by width generated during the scratching process. Additionally, the percentage of scratches exhibiting cracks showed some differences as shown in Tables 11-18. Note that the knee stress changes with surface CS in the modified methods. Without wishing to be bound by any particular theory, the scratch tests in this example indicate that a combination of the stress at the surface, the location of the knee, and the stress at the knee, and possibly even the index of the profile, may play a role in certain scratch events and the visibility of the scratches. Various scratch tests were performed on the profile shown in Figure 23, and Examples 6B-D, which were modified to obtain higher CS, performed better on average against scratches when compared to Example 6A.
[0304] FIG. 26 shows the drop performance of samples on 30 grit abrasive paper from various conditions in Examples 6A-D compared to a reference glass with nominal values of 57.5 mol% SiO2, 16.5 mol% Al2O3, 16.5 mol% Na2O, 2.8 mol% MgO, 6.5 mol% P2O5, and 0.05 mol% SnO2. It can be seen that Examples 6A-D have similar performance and show improved drop performance compared to the reference glass. In some embodiments, the desired stress profile is resistance to fracture after dropping the surface onto a rough surface. In FIG. 26, a controlled drop test of samples on 30 grit abrasive paper from various conditions in the glass of the present invention is shown compared to the reference glass with the most fracture-resistant profile for this test among the cover glasses on products currently on the market. It can be seen that all tested profiles with a large compression depth DOC of >130 μm have similar performance in this test and show substantial improvement in drop performance compared to the reference glass. From this, the inventors believe that these nonlinear diffusion curvature profiles with spikes and large DOC can result in significant improvements in drop performance and in some cases improved scratch resistance.
[0305] Example 7 Example 7A and Comparative Examples 7B-7D included glass substrates having a thickness of 0.8 mm and a nominal composition of 64 mol% SiO2, 15 mol% Al2O3, 2.4 mol% B2O3, 9.2 mol% Na2O, 5.9 mol% Li2O, 1.2 mol% ZnO, 2.5 mol% P2O5, 0.05 mol% SnO2, and using three different mixtures of NaNO3 and KNO3, according to one or more embodiments of the present disclosure. The glass substrates of Examples 7A-7D were ion-exchanged in a molten salt bath including the conditions shown in Table 19, and the resulting properties are also listed in that table.
[0306] [Table 19]
[0307] Figure 36 shows three stress profiles, corresponding to Comparative Examples 7B-D, measured by RNF (refractive near-field scanning), namely curves 2801, 2802, and 2803. Due to the limited resolution of the RNF, the surface CS of the spikes are not well shown (the spikes are rounded in the RNF profiles and have smaller maximum stresses than the actual CS). The salt mixtures have 70, 40, and 28 wt% NaNO3, the remainder of the mass is KNO3, and due to the effect of eliminating salt contamination, a maximum of 0.5 wt% silicic acid. This corresponds to a Na:K molar ratio in the salt of 2.78, 0.79, and 0.46, respectively. All three profiles were obtained using ion exchange conditions resulting in stable DOC and high CT regimes, obtained by ion exchange at 390 C for about 3.5 hours (curve 2802), or at 380 C for about 4 hours (curves 2801 and 2803). As can be seen, decreasing the Na:K molar ratio substantially increases the surface Cs of the spike, which is due to the stress Cs at the base of the spike. kThis is achieved at the expense of a significant reduction in the compressive stress area beyond the spike (the integral over depth of the compressive stress from the base of the spike to the DOC). A phone with a cover glass having a stress profile similar to the first SIOX profile of FIG. 36 (70% NaNO3, curve 2801) has good resistance to fracture by deep damage introduction when dropped on a rough surface, but may have a tendency to fracture by overstressing of shallow scratches around the edge or on the backside due to the relatively low surface CS (e.g., when dropped on its edge or hit by a blunt object). A phone with a cover glass having a stress profile with the third stress profile (28% NaNO3, curve 2803) has good resistance to fracture by significant overstressing of shallow scratches, but is less resistant to fracture by deep damage introduction from violent contact. The intermediate profile (40 wt.% NaNO3, curve 2802) represents a compromise between the two major fracture modes. However, it would be beneficial to have a spike with a higher CS than the third profile (28% NaNO3, curve 2803) while having a similar compressive integral over the entire compressive zone (e.g., similar to curve 2801, the first profile of 70% NaNO3). It would be even more beneficial to increase the compressive stress at depths >0.3 DOC and further increase the DOC. Curve 2804 obtained with some embodiments disclosed herein achieves these objectives.
[0308] FIG. 36 shows a DIOX stress profile curve 2804 (Example 7A) according to some embodiments of the invention along with three SIOX profiles (Curves 2801-2803 of Comparative Examples 7B-7D) for the same Corning Incorporated glass having a nominal composition of 64 mol% SiO, 15 mol% AlO, 2.4 mol% BO, 9.2 mol% NaO, 5.9 mol% LiO, 1.2 mol% ZnO, 2.5 mol% P0, and 0.05 mol% SnO of a thickness of 0.8 mm. The DIOX profile was obtained by a first step of ion exchange at 380° C. for 4 hours in a salt with 70 wt. % NaNO3 and 30 wt. % KNO3 (Na:K ratio is 2.78) and a second step of ion exchange at 380° C. for 40 minutes in a salt with 7 wt. % NaNO3 and 93 wt. % KNO3 (Na:K ratio is about 0.09). As can be seen, the Na:K ratio in the second bath is about 1 / 31 of that in the first bath, and the effective ion exchange time of the second bath is about 1 / 6 of the first step ion exchange time. In the first step, the concentration of K leads to a surface CS of about 400 MPa and a DOL of about 9.4 μm. sp The second step increased the CS of the spike to about 800 MPa and the effective DOL of about 8.7 μm. sp In this particular example, the DOL sp Note that the apparent decrease in DOL is an artifact caused by the regular change of the spike from a nearly linear shape after step 1 to a somewhat curved shape with positive curvature after step 2. The DOL in both cases sp is calculated assuming linear spikes, so DOL sp appears to be somewhat smaller after step 2. This primarily means that the highly compressed portion of the spike that occurs during step 2 is somewhat shallower than the original depth of the spike after step 1. In another example, especially for thinner glasses (e.g., 0.5 mm) where the effective diffusion time of the second step is only 1 / 3 to 1 / 5 shorter than that of the first step, and where the change in CS from step 1 to step 2 is less pronounced, the effective DOL after step 2 issp DOL of the first step sp It is similar to and often somewhat larger than
[0309] A sample was prepared according to Example 7A and the Knoop scratch threshold (KST) was measured as described above. The KST was greater than 10 and less than 16.
[0310] Additionally, IBoS testing was performed on the samples using a stainless steel ball having a weight of 4.2 grams and a diameter of 10 mm and 30 grit non-laminated abrasive paper. The results of the IBoS testing are shown in FIG. 37. In particular, the average drop height that survived was 76 cm. Sixty percent (three out of five) of the samples survived a drop height of more than 80 cm. In particular, the reinforced glass articles had a survival rate of at least 60% when subjected to an IBoS test using a 4.2 g stainless steel ball having a diameter of 10 mm from a height of about 80 cm onto 30 grit abrasive paper that was placed on the glass surface such that there was a 100 μm gap between the abrasive paper and the glass surface, where the survival rate was based on testing of at least five samples.
[0311] Impact threshold tests were then performed using an apparatus as shown in Figures 29 to 35, i.e. on both major faces of the sample and on its edges. The results are shown in Figure 38 for face impact and in Figure 39 for edge impact.
[0312] Specifically for the face impact test, 180 grit abrasive paper was used to subject a 110 mm x 56 mm x 0.8 mm substrate with bullnose ends to a 0.4 m bend radius as per Figure 34. As can be seen from Figure 38, the sample according to Example 7 was able to survive impact forces of more than 200 N, such as 250 N or more, 300 N or more, 350 N or more, 400 N or more, 450 N or more, 500 N or more, 550 N or more, 600 N or more, 650 N or more, 700 N or more, 750 N or more, 800 N or more, and even 850 N or more. In fact, the sample of Example 7A reached a maximum impact load of 851 N and did not break.
[0313] The results of the Example 7A sample are compared to another glass, not necessarily Comparative Examples 7B-D, which is indicated as "Comparative" in FIG. 38. In particular, the comparative sample set consists of a commercially available alkali aluminosilicate glass (Dragontrail® glass, manufactured by Asahi Glass Company) of identical composition (nominal composition is about 65 mol% SiO2, about 8 mol% Al2O3, about 12 mol% Na2O, about 4 mol% K2O, about 0.3 mol% CaO, about 10 mol% MgO, and about 0.5 mol% ZrO2) and thickness (0.8 mm). The comparative sample set glasses were ion-exchanged to have a compression depth of layer DOL of 24 μm and a surface compressive stress CS of 804 MPa. In contrast, the comparative sample set samples reached an average impact force of only about 152 N, with only 3 out of 10 (or 30%) samples surviving impact forces greater than 200 N. Therefore, the tempered glass according to the present disclosure, particularly according to Example 7, is suitable for use in mobile devices that may be dropped.
[0314] Next, the samples according to Example 7A were tested in the configuration of FIG. 35 to evaluate the survival when the glass edge is impacted by violent contact. The results are shown in FIG. 39. The arrows shown on the glass of Example 7A highlight the impact force (N) or impact energy (J) at which the glass was found to begin to break, with higher values resulting in improved performance. For the samples of Example 7A, all samples tested survived the condition of 1.28 J, but then all broke at 1.58 J. All samples used to generate this plot were ion-exchanged and had a 2.5D shape with a thickness of about 0.8 mm at the center and about 0.3 mm at the edge. Thus, according to some embodiments, the glass-based article made according to Example 7A can survive edge impact forces of 400 N or more (e.g., 450 N) or impact energies of 1.28 J or more.
[0315] It will be apparent to those skilled in the art that various modifications and variations can be made in the present disclosure without departing from the spirit or scope of the disclosure.
[0316] For example, the glass-based articles disclosed herein can be incorporated into another article, such as an article having a display (i.e., a display article) (e.g., consumer electronics, including cell phones, tablets, computers, navigation systems, wearable devices (e.g., watches), etc.), a building article, a transportation article (e.g., automobiles, trains, aircraft, seagoing vessels, etc.), an appliance, or any article in which some degree of transparency, scratch resistance, abrasion resistance, or combinations thereof, would be beneficial. Representative articles in which any of the glass-based articles disclosed herein may be incorporated are shown in Figures 40A and 40B. In particular, Figures 40A and 40B show a consumer electronic device 4100 including a housing 4102 having a front surface 4104, a back surface 4106, and a side surface 4108, electrical components (not shown) at least partially or completely residing within the housing and including at least a controller, memory, and a display 4110 at or near the front surface of the housing, and a cover substrate 4112 at or on the front surface of the housing to cover the display. In some embodiments, the cover substrate 4112 can include any of the glass-based articles disclosed herein. In some embodiments, at least one of a portion of the housing or the cover glass comprises a glass-based article disclosed herein.
[0317] Further, for example, various features can be combined according to the following exemplary embodiments.
[0318] Embodiment 1. A method for manufacturing a semiconductor device comprising the steps of: a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm; The stress profile extending through the thickness (t) A glass-based article comprising: at least one point of the stress profile within a first thickness range of about 0·t up to 0.020·t and greater than 0.98·t includes a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer; all points of the stress profile within a second thickness range of about 0.035·t to less than 0.965·t include a tangent having a slope of about −15 MPa / micrometer to about 15 MPa / micrometer; The stress profile includes a surface CS of about 200 MPa to about 1100 MPa; The stress profile is for a glass-based article containing a DOC in the range of approximately 0.1·t to 0.25·t.
[0319] Embodiment 2. The glass-based article of embodiment 1, wherein all points of the stress profile within the second thickness range include a tangent having a slope from about -2 MPa / micrometer to about 2 MPa / micrometer.
[0320] Embodiment 3. The glass-based article of embodiment 1, wherein the second thickness range extends from 0.025·t to 0.035·t and from 0.965·t to 0.975·t, and all points of the stress profile in the second thickness range extension include a tangent having a slope from about −15 MPa / micrometer to about 15 MPa / micrometer.
[0321] Embodiment 4. The glass-based article of embodiment 3, wherein all points of the stress profile within the second thickness range include a tangent having a slope from about -2 MPa / micrometer to about 2 MPa / micrometer.
[0322] Embodiment 5. The glass-based article of embodiment 1 or embodiment 3, wherein the second thickness range is further expanded from 0.02·t to 0.025·t and from 0.975·t to 0.98·t, and all points of the stress profile in the further expansion of the second thickness range include a tangent having a slope from about −15 MPa / micrometer to about 15 MPa / micrometer.
[0323]
[0023] Embodiment 6. The glass-based article of embodiment 5, wherein all points of the stress profile in the further expansion of the second thickness range include a tangent having a slope from about -2 MPa / micrometer to about 2 MPa / micrometer.
[0324] Embodiment 7. The glass-based article of any one of embodiments 1-6, wherein the stress profile within the second thickness range forms a power law profile having a power exponent, the power exponent being between about 1.2 and 3.2.
[0325] Embodiment 8. The glass-based article of embodiment 7, wherein the power exponent is about 1.3 to 2.8.
[0326] Embodiment 9. The glass-based article of any one of embodiments 1-8, wherein the surface CS is from about 300, 350, 400, 450, 500, 550, 600, 610, 620 MPa to about 650, 700, 750, 800, 850, 900, 950, 1000, or 1100 MPa.
[0327] Embodiment 10. The glass-based article of any one of embodiments 1-9, wherein at least one point of the stress profile within the first thickness range comprises a tangent having a slope of from about -170 MPa / micrometer to about -30 MPa / micrometer or from about 30 MPa / micrometer to about 170 MPa / micrometer.
[0328] Embodiment 11. The glass-based article of embodiment 10, wherein at least one point of the stress profile within the first thickness range comprises a tangent having a slope of from about -140 MPa / micrometer to about -35 MPa / micrometer or from about 35 MPa / micrometer to about 140 MPa / micrometer.
[0329] Embodiment 12. The glass-based article of embodiment 1, wherein the first thickness range is expanded from about 0.02·t up to 0.025·t and from greater than 0.975·t to 0.98·t, and at least one point of the stress profile within the expanded first thickness range comprises a tangent having a slope of about -200 MPa / micrometer to about -25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer.
[0330] Embodiment 13. The glass-based article of embodiment 12, wherein at least one point of the stress profile within the expanded first thickness range comprises a tangent having a slope of from about -170 MPa / micrometer to about -30 MPa / micrometer or from about 30 MPa / micrometer to about 170 MPa / micrometer.
[0331] Embodiment 14. The glass-based article of embodiment 13, wherein at least one point of the stress profile within the expanded first thickness range comprises a tangent having a slope of from about -140 MPa / micrometer to about -35 MPa / micrometer or from about 35 MPa / micrometer to about 140 MPa / micrometer.
[0332] Embodiment 15. The glass-based article of embodiment 1 or embodiments 12-14, wherein the first thickness range is further expanded from about 0.025·t up to 0.035·t and from greater than 0.965·t up to about 0.975·t, and at least one point of the stress profile in the further expansion of the first thickness range comprises a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer.
[0333] Embodiment 16. The glass-based article of embodiment 15, wherein at least one point of the stress profile in the further expansion of the first thickness range comprises a tangent having a slope of about -170 MPa / micrometer to about -30 MPa / micrometer or about 30 MPa / micrometer to about 170 MPa / micrometer.
[0334] Embodiment 17. The glass-based article of embodiment 16, wherein at least one point of the stress profile in the further expansion of the first thickness range comprises a tangent having a slope of about -140 MPa / micrometer to about -35 MPa / micrometer or about 35 MPa / micrometer to about 140 MPa / micrometer.
[0335] Embodiment 18. The glass-based article of any one of embodiments 1-17, wherein the first thickness range is obtained by ion exchange in a potassium-containing salt.
[0336] Embodiment 19. The glass-based article of any one of embodiments 1-18, wherein the second thickness range is obtained by ion-exchange in a Na-containing salt.
[0337] Embodiment 20. The glass-based article of any one of embodiments 1-19, wherein the stress profile is obtained using one ion-exchange step.
[0338] Embodiment 21. The glass-based article of any one of embodiments 1-19, wherein the stress profile is obtained using two or more ion-exchange steps.
[0339] Embodiment 22. The glass-based article of any one of embodiments 1-21, wherein the surface CS is about 690 MPa to 950 MPa.
[0340]
[0041] Embodiment 23. The glass-based article of any one of embodiments 1-22, comprising a composition comprising about 0.5 mol% to about 10 mol% P2O5.
[0341] Embodiment 24. A central surface comprising about 2 to about 20 mol % LiO; The stress profile extending through the thickness (t) A glass-based article comprising: at least one point of the stress profile within a first thickness range of about 0·t up to 0.020·t and greater than 0.98·t includes a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer; The stress profile includes a surface CS of about 200 MPa to about 1100 MPa; The stress profile is for a glass-based article containing a DOC in the range of approximately 0.05·t to 0.25·t.
[0342] Embodiment 25. The glass-based article of embodiment 24, wherein the first thickness range is obtained by ion exchange in a potassium-containing salt.
[0343] Embodiment 26. The glass-based article of embodiment 24, wherein the second thickness range is obtained by ion-exchange in a Na-containing salt or a K-containing salt.
[0344] Embodiment 27. The glass-based article of any one of embodiments 24-26, wherein the stress profile is obtained using one ion-exchange step.
[0345] Embodiment 28. The glass-based article of one of embodiments 24-26, wherein the stress profile is obtained using two or more ion-exchange steps.
[0346] Embodiment 29. The glass-based article of any one of embodiments 24-28, wherein the surface CS is in the range of about 690 MPa to 950 MPa.
[0347] Embodiment 30. The glass-based article of any one of embodiments 24-29, wherein the stress profile within the second thickness range forms a power law profile having a power exponent, the power exponent being about 1.2 to 3.4.
[0348] Embodiment 31. The glass-based article of embodiment 30, wherein the power exponent is about 1.3 to 2.8.
[0349] Embodiment 32. The glass-based article of any one of embodiments 24-31, comprising a composition comprising about 0.5 mol % to about 10 mol % P2O5.
[0350] Embodiment 33. The glass-based article of any one of embodiments 24-32, wherein the central surface further comprises a composition comprising about 0.5 mol % to about 20 mol % Na2O.
[0351] Embodiment 34. The glass-based article of any one of embodiments 24-33, wherein the central surface further comprises a composition comprising about 2 mol% to about 10 mol% Li2O.
[0352] Embodiment 35. The glass-based article of embodiment 33 or embodiment 34, wherein the concentration of Na2O within the center plane of the glass article is from about 5 mol% to about 16 mol%.
[0353] Embodiment 36. The glass-based article of embodiment 33 or embodiment 34, wherein the concentration of Na2O within the center plane of the glass article is about 10 mol% to 15 mol%.
[0354] Embodiment 37. The glass-based article of embodiment 36, wherein the concentration of Li2O within the central plane of the glass article is about 3 mol% to 10 mol%.
[0355] Embodiment 38. The glass-based article of any one of embodiments 24-37, wherein over a thickness of 0·t up to 0.3·t, the stress profile further comprises a tangent line with a minimum slope and a tangent line with a maximum slope, and the difference between the maximum slope and the minimum slope is 3.5 MPa / micrometer or less.
[0356] Embodiment 39. The glass-based article of any one of embodiments 24-38, wherein all points in the stress profile between thicknesses of about 0·t to about 0.3·t and greater than 0.7·t include a tangent that is less than about −0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer.
[0357]
[0046] Embodiment 40. The glass-based article of any one of embodiments 24-39, further comprising a potassium DOL extending across the first thickness range.
[0358] Embodiment 41. The glass-based article of any one of embodiments 24-40, further comprising a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm.
[0359] Embodiment 42. The glass-based article of any one of embodiments 1-23, wherein over a thickness of 0·t up to 0.3·t, the stress profile further comprises a tangent line with a minimum slope and a tangent line with a maximum slope, and the difference between the maximum slope and the minimum slope is 3.5 MPa / micrometer or less.
[0360] Embodiment 43. The glass-based article of any one of embodiments 1-23, or 42, wherein all points in the stress profile between thicknesses of about 0·t to about 0.3·t and greater than 0.7·t include a tangent that is less than about −0.1 MPa / micrometer or greater than about 0.1 MPa / micrometer.
[0361] Embodiment 44. The glass-based article of any one of embodiments 1-23, or 42-43, further comprising a potassium DOL extending across the first thickness range.
[0362] Embodiment 45. The glass-based article of any one of embodiments 1-23 or 41-44, further comprising a concentration of metal oxide that decreases from the first surface to a value at a point between the first surface and the second surface, and increases from that value to the second surface.
[0363] Embodiment 46. A method of chemically strengthening a glass-based substrate comprising a first major surface, a second major surface, an average thickness t extending perpendicularly between the first and second major surfaces, and an edge extending between the first and second major surfaces, comprising: performing a first IOX step by holding the glass-based substrate in a first bath containing a mixture of sodium ions and potassium ions for a first time; After the first IOX step, performing a second IOX step by holding the glass-based substrate in a second bath containing a mixture of sodium ions and potassium ions for a second time to form a stress profile in the glass-based substrate, the stress profile having a CS region and a CT region. Including, The method wherein the second bath has a mole ratio of Na:K that is 1 / 3 to 1 / 10 of the mole ratio of Na:K of the first bath.
[0364] Embodiment 47. The method of embodiment 46, wherein both steps of ion exchange are completed in a bath containing both a Na-containing salt and a K-containing salt, and the ratio of Na ions to K ions in the first bath is one of (i) 2.5 times or more, (ii) 3 times or more, (iii) 5 times or more, or (iv) 8 times or more than the ratio of Na ions to K ions in the second bath, and is one of (i) 800 times or less, (ii) 600 times or less, (iii) 500 times or less, and (iv) 400 times or less.
[0365] Embodiment 48. The method of any one of embodiments 46-47, wherein the second bath has a molar ratio of Na to K that is one of: (i) 0.03 or more, (ii) 0.04 or more, (iii) 0.047 or more, (iv) 0.06 or more, and (v) 0.07 or more, and one of: (i) 0.4 or less, (ii) 0.35 or less, (ii) 0.30 or less, (iii) 0.21 or less, (iv) 0.16 or less, or (v) 0.13 or less.
[0366] Embodiment 49. The method of any one of embodiments 46-48, wherein the effective diffusion time of the second IOX step is one of: (i) 1 / 20 to 1 / 2 of the first step, (ii) 1 / 20 to 1 / 3 of the first step, and (iii) 1 / 20 to 1 / 4 of the first step.
[0367] Embodiment 50. The method of any one of embodiments 46-49, wherein the surface CS of the glass-based article after the second IOX step is one of: (i) 600 MPa or more, (ii) 650 MPa or more, (iii) 700 MPa or more, (iv) 750 MPa or more, (v) 800 MPa or more, (vi) 850 MPa or more.
[0368] Embodiment 51. DOL sp(i) is within 0.5-1.5% of the thickness when the thickness is 1-1.3 mm, (ii) is within 0.6-2% of the thickness when the thickness is 0.8-1 mm, (iii) is within 0.7-2.5% of the thickness when the thickness is 0.65-0.8 mm, (iv) is within 0.9-3% of the thickness when the thickness is 0.5-0.65 mm, and (v) is within 1-3% when the thickness is 0.3-0.5 mm.
[0369] Embodiment 52. The method of any one of embodiments 46-51, wherein the DOC is one of: (i) 0.1t or more; (ii) 0.15t or more; (iii) 0.2t or more.
[0370] Embodiment 53. The method of any one of embodiments 46-52, wherein the stress profile in the CT domain comprises a power law profile having a power exponent, the power exponent being one of: (i) 1 to 3.4, (ii) 1.2 to 3.0, and (iii) 1.7 to 2.6.
[0371] Embodiment 54. The method of any one of embodiments 46-53, wherein the Knoop scratch threshold of the strengthened glass-based substrate is greater than 10 N.
[0372] Embodiment 55. The method of embodiment 54, wherein the Knoop scratch threshold of the reinforced glass-based substrate is less than 16N.
[0373] Embodiment 56. The method of any one of embodiments 46-55, wherein the reinforced glass-based substrate has at least 60% survival when subjected to an inverted ball drop test using a 4.2 g stainless steel ball having a diameter of 10 mm from a height of about 80 cm onto 30 grit abrasive paper placed on the glass surface such that there is a 100 μm air gap between the abrasive paper and the glass surface, the survival rate being based on testing of at least five samples.
[0374] Embodiment 57. The method of any one of embodiments 46 to 56, wherein the reinforced glass-based substrate has a survival rate of (i) 60% or more, (ii) 70% or more, (iii) 80% or more, (iv) 90% or more, or (v) 100% or less when impacted on one of the first and second major surfaces with a force of (i) 200N or more, (ii) 250N or more, (iii) 300N or more, (iv) 350N or more, (v) 400N or more, (vi) 450N or more, (vii) 500N or more, (viii) 550N or more, (ix) 600N or more, (x) 650N or more, (xi) 700N or more, (xii) 750N or more, (xiii) 800N or more, or (xiv) 850N or more according to a surface impact threshold test using a 180 grit abrasive.
[0375] Embodiment 58. The method of embodiment 57, wherein the reinforced glass-based substrate has a survival rate of 100% or less when impacted on one of the first and second major surfaces with a force of 900 N or less according to a Surface Impact Threshold Test using 180 grit abrasive.
[0376] Embodiment 59. The method of any one of embodiments 46-56, wherein the strengthened glass-based substrate is capable of surviving an end impact of (i) greater than 300 N, (ii) equal to or greater than 400 N, (iii) equal to or greater than 450 N, or (i) greater than 0.68 J, (ii) equal to or greater than 0.97 J, (iii) equal to or greater than 1.28 J.
[0377] Embodiment 60. The method of embodiment 59, wherein the strengthened glass-based substrate can survive an end impact of less than 500 N or an end impact of less than 1.58 J.
[0378] Embodiment 61. The glass-based article of any one of embodiments 1-45, wherein the strengthened glass-based substrate has a Knoop scratch threshold of greater than 10 N.
[0379] Embodiment 62. The glass-based article of embodiment 61, wherein the strengthened glass-based substrate has a Knoop scratch threshold of less than 16N.
[0380] Embodiment 63. The glass-based article of any one of embodiments 1-45, wherein the reinforced glass-based substrate has at least 60% survival when subjected to an inverted ball drop test using a 4.2 g stainless steel ball having a diameter of 10 mm from a height of about 80 cm onto 30 grit abrasive paper placed on the glass surface such that there is a 100 μm air gap between the abrasive paper and the glass surface, the survival rate being based on testing of at least 5 samples.
[0381] Embodiment 64. The glass-based article of any one of embodiments 1 to 45, wherein the reinforced glass-based substrate has a survival rate of (i) 60% or more, (ii) 70% or more, (iii) 80% or more, (iv) 90% or more, or (v) 100% or less when impacted against one of the first and second main surfaces with a force of (i) 200N or more, (ii) 250N or more, (iii) 300N or more, (iv) 350N or more, (v) 400N or more, (vi) 450N or more, (vii) 500N or more, (viii) 550N or more, (ix) 600N or more, (x) 650N or more, (xi) 700N or more, (xii) 750N or more, (xiii) 800N or more, or (xiv) 850N or more according to a surface impact threshold test using a 180 grit abrasive.
[0382] Embodiment 65. The glass-based article of embodiment 64, wherein the reinforced glass-based substrate has a survival rate of 100% or less when impacted on one of the first and second major surfaces with a force of 900 N or less according to a Surface Impact Threshold Test using a 180 grit abrasive.
[0383] Embodiment 66. The glass-based article of any one of embodiments 1-45, wherein the strengthened glass-based substrate is capable of surviving an end impact of (i) greater than 300 N, (ii) equal to or greater than 400 N, (iii) equal to or greater than 450 N, or (i) greater than 0.68 J, (ii) equal to or greater than 0.97 J, (iii) equal to or greater than 1.28 J.
[0384] Embodiment 67. The glass-based article of embodiment 66, wherein the strengthened glass-based substrate can survive an edge impact of less than 500 N or an edge impact of less than 1.58 J.
[0385] Embodiment 68. A consumer electronic product, comprising: a housing having a front, a back, and sides; electrical components disposed at least partially within the housing, the electrical components including at least a controller, a memory, and a display, the display being disposed at or near a front surface of the housing; A cover substrate disposed on the display; Including, A consumer electronic product, wherein at least one of a portion of the housing or a cover substrate comprises the glass-based article of any one of embodiments 1-45 or 61-67. EMBODIMENT 69 A method of chemically strengthening a glass-based substrate comprising a first main surface, a second main surface, an average thickness t extending perpendicularly between the first and second main surfaces, and an edge extending between the first and second main surfaces, comprising: performing a first IOX step by holding the glass-based substrate in a first bath containing a mixture of sodium ions and potassium ions for a first time; performing a second IOX step after the first IOX step by holding the glass-based substrate in a second bath comprising a mixture of sodium ions and potassium ions for a second time period to form a stress profile in the glass-based substrate, the stress profile having a compressive stress CT region and a central tensile stress CS region, the stress profile extending along a thickness (t) according to a mathematical formula that is a function of the thickness (t); at least one point of the stress profile equation within a first thickness range of about 0·t to 0.020·t and greater than 0.98·t includes a tangent having a slope of about −200 MPa / micrometer to about −25 MPa / micrometer or about 25 MPa / micrometer to about 200 MPa / micrometer; all points of the stress profile equation within a second thickness range of about 0.035·t to about 0.965·t inclusive include a tangent having a slope of about −15 MPa / micrometer to about 15 MPa / micrometer; a mathematical equation of the stress profile within the second thickness range forms a power law profile having a power exponent, the power exponent being between about 1.2 and about 3.4; Including the maximum surface compressive stress CS of about 200MPa to about 1100MPa, The stress profile includes a compression depth DOC in the range of about 0.05·t to 0.25·t; 11. A method according to claim 10, wherein the second bath has a molar ratio of Na:K that is 1 / 3 to 1 / 10 of the Na:K molar ratio of the first bath. EMBODIMENT 70 70. The method of claim 69, wherein the glass-based article after the second IOX step has a maximum surface compressive stress CS of 600 MPa or more, a compression depth DOC of 0.14·t or more, and a maximum central tension CT of 80 MPa or less. EMBODIMENT 71 71. The method of embodiment 70, wherein both steps of ion exchange are completed in a bath containing both a Na-containing salt and a K-containing salt, and the ratio of Na ions to K ions in the first bath is 3 to 8 times or more greater than the ratio of Na ions to K ions in the second bath. EMBODIMENT 72 71. The method of embodiment 70, wherein the second bath has a molar ratio of Na to K between 0.03 and 0.4. EMBODIMENT 73 71. The method of embodiment 70, wherein the effective diffusion time of the second IOX step is 1 / 20 to 1 / 2 of that of the first step. EMBODIMENT 74 The method of embodiment 70, wherein the depth of layer DOLsp is (i) in the range of 0.5 to 1.5% of the thickness when the thickness is 1 to 1.3 mm, (ii) in the range of 0.6 to 2% of the thickness when the thickness is 0.8 to 1 mm, (iii) in the range of 0.7 to 2.5% of the thickness when the thickness is 0.65 to 0.8 mm, (iv) in the range of 0.9 to 3% of the thickness when the thickness is 0.5 to 0.65 mm, and (v) in the range of 1 to 3% when the thickness is 0.3 to 0.5 mm. EMBODIMENT 75 71. The method of embodiment 70, wherein the mathematical expression in the central tension CT region comprises a power law profile having an exponent, the exponent being between 1 and 3.4. EMBODIMENT 76 (i) The Knoop scratch lateral crack threshold of the tempered glass-based substrate is greater than 10 N and less than 16 N; (ii) the reinforced glass-based substrate has a survival rate of 40% to 100% when impacted against one of the first and second principal surfaces with a force of 400 N or more in accordance with a surface impact threshold test using a 180 grit abrasive; and (iii) the reinforced glass-based substrate is capable of surviving an edge impact of greater than 300N and less than 500N or greater than 0.68J and less than 1.58J according to an edge impact threshold test using a 30 grit abrasive: 71. The method of embodiment 70, characterized by at least one of the following: EMBODIMENT 77 71. The method of embodiment 70, wherein the thickness (t) is 1 mm or less.
Claims
1. a first surface and a second surface opposite the first surface, the first surface and the second surface defining a thickness (t) in the range of 0.1 mm to 2 mm; a stress profile extending along the thickness (t) according to a mathematical formula which is a function of the thickness (t); A glass-based article comprising: all points of the stress profile equation within a first thickness range from 0 t up to 0.020 t and greater than 0.98 t include tangents with slopes between −200 MPa / micrometer and −25 MPa / micrometer or between 25 MPa / micrometer and 200 MPa / micrometer; all points of the stress profile equation within a second thickness range of 0.035 t to less than 0.965 t include a tangent having a slope between −15 MPa / micrometer and 15 MPa / micrometer; a mathematical equation for the stress profile within the second thickness range forming a power law profile having an exponent between 1.2 and 3.2; The stress profile comprises a surface compressive stress of 300 MPa to 1100 MPa and a maximum central tension of 50 MPa or greater.
2. 10. The glass-based article of claim 1, wherein the stress profile comprises a compression depth in the range of 0.1·t to 0.25·t.
3. 2. The glass-based article of claim 1, wherein the maximum central tension is less than or equal to 80 MPa.
4. 10. The glass-based article of claim 1, wherein all points of the stress profile within the second thickness range include a tangent having a slope between -2 MPa / micrometer and 2 MPa / micrometer.
5. 10. The glass-based article of claim 1, wherein the first thickness range is expanded from 0.02·t up to 0.025·t and from greater than 0.975·t to 0.98·t, and all points of the stress profile equation within the expanded first thickness range include a tangent with a slope from −200 MPa / micrometer to −25 MPa / micrometer or from 25 MPa / micrometer to 200 MPa / micrometer.
6. 6. The glass-based article of claim 5, wherein the first thickness range is further expanded from 0.025 t up to 0.035 t and from greater than 0.965 t up to 0.975 t, and all points of the stress profile equation in the further expansion of the first thickness range include a tangent with a slope between -200 MPa / micrometer and -25 MPa / micrometer or between 25 MPa / micrometer and 200 MPa / micrometer.
7. 7. The glass-based article of any one of claims 1 to 6, wherein the thickness (t) is 1 mm or less, the surface compressive stress is 500 MPa or more, and the compression depth is 0.14·t or more.
8. 7. The glass-based article of any one of claims 1 to 6, further comprising a potassium layer depth extending across the first thickness range.
9. (i) the Knoop scratch lateral crack threshold of the glass-based article is greater than 10 N and less than 16 N; (ii) the glass-based article has a survival rate of 40% to 100% when impacted on one of the first surface and the second surface with a force of 400 N or more according to a surface impact threshold test using a 180 grit abrasive; and (iii) the glass-based article is capable of surviving an edge impact of greater than 300N and less than 500N or greater than 0.68J and less than 1.58J according to an Edge Impact Threshold Test using a 30 grit abrasive. The glass-based article according to any one of claims 1 to 6, characterized by at least one of the following:
10. The central plane is 2 mol% to 20 mol% Li 2 The glass-based article of any one of claims 1 to 6, further comprising a composition comprising O.
11. The central plane is 0.5 mol % to 20 mol % Na 2 11. The glass-based article of claim 10, further comprising a composition comprising O.
12. 0.5 mol% to 10 mol% P 2 O 5 12. The glass-based article of claim 11 comprising a composition comprising:
13. The glass-based article of any one of claims 1 to 6, wherein the surface compressive stress is in the range of 690 MPa to 1100 MPa.
Citation Information
Patent Citations
Glass board for recording medium, recording medium using glass board and manufacture of glass board for recording medium
JP1999328601A
A two-step method for strengthening glass
JP2013536155A
Strengthened glass with deep depth of compression
US20150259244A1
Strengthening glass by multiple alkali ion exchange
US3433611A
Chemically strengthened glass and method for producing same
WO2013047675A1